Alpha-Fe-containing rare earth-iron-nitrogen magnetic powder, method for producing same, magnetic material for magnetic field amplification, and magnetic material for ultrahigh frequency absorption

By using the structural design and process of α-Fe rare earth-iron-nitrogen-based magnetic powders in magnetic materials, a phosphorus compound coating portion with sea-island structure is formed, which solves the problem of insufficient efficiency of existing materials in high-frequency and ultra-high-frequency regions, and realizes low iron loss and high-efficiency magnetic materials.

CN119654690APending Publication Date: 2025-03-18NICHIA CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380060324.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-04-14
Filing Date
2023-08-10
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

Existing magnetic materials are inefficient in high-frequency and ultra-high-frequency regions and lack materials that can meet the absorption requirements of ultra-wide frequency bands.

Method used

A magnetic powder containing rare earths-iron-nitrogen is used, and its structure includes a nuclear region and an α-Fe-containing region. The nuclear region contains rare earths, Fe and N. The α-Fe-containing region has a sea-island structure, and a phosphorus compound coating is formed through phosphorus treatment and oxidation processes.

Benefits of technology

It realizes low iron loss and high efficiency magnetic materials in high-frequency and ultra-high frequency regions, and has excellent high-frequency characteristics and ultra-high frequency absorption capabilities.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119654690A_ABST
    Figure CN119654690A_ABST
Patent Text Reader

Abstract

Provided is a magnetic powder having excellent high-frequency characteristics, which has low iron loss and excellent efficiency even when a high frequency is applied. An [alpha]-Fe-containing rare earth-iron-nitrogen-based magnetic powder having: a core region containing a rare earth R (R is at least one selected from the group consisting of Y, Ce, Pr, Nd, Gd, Tb, Dy, Ho, Er, Tm, Lu and Sm, and when Sm is included, Sm is less than 50 at% with respect to the entire R component), Fe, and N, and an [alpha]-Fe-containing region on the outside of the core region; the [alpha]-Fe-containing region contains [alpha]-Fe and at least one element selected from the group consisting of oxides, nitrides, and nitrogen oxides of the rare earth R.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an α-Fe-containing rare earth-iron-nitrogen magnetic powder, a method for producing the same, a magnetic material for amplifying a magnetic field, and a magnetic material for absorbing ultrahigh frequency. Background Art

[0002] In recent years, with the miniaturization and multifunctionalization of equipment and the acceleration of computing processing speed, the high-frequency driving frequency is developing, and the popularity of high-frequency and ultra-high-frequency equipment is expanding. In particular, the development of power devices used in the high-frequency region from above 1MHz to below 1GHz has attracted much attention. For example, as a device for high-frequency / high-output wireless and power electronics, it can be predicted that the market for GaN electronic devices will expand significantly in the future. As for the high-frequency GaN circuit for power electronics, not only GaN devices are required, but also the high-frequency passive components. For example, in GaN contactless power supply, since the frequency handled exceeds 10MHz, a coil with a magnetic core material that can follow the high frequency is required. However, the current situation is that there is no magnetic core material with excellent high-frequency characteristics, so air-core coils have to be used. Even if GaN can be applied to achieve high frequency and miniaturization of the device, there is still a problem of increasing the overall circuit size.

[0003] Next, the development of information infrastructure in the ultra-high frequency region of 1 GHz to 1 THz has attracted much attention. There are various demands for the high-frequency characteristics of spurious materials that absorb signals in the region above 1 GHz and below 10 GHz in the case of 5G, above 10 GHz and below 100 GHz in the case of 5G+, and above 100 GHz and below 1 THz in the case of 6G, and their higher harmonics, etc., and their necessity is increasing recently. In particular, in reality, there are no materials that absorb ultra-high frequencies in a wide band above 1 GHz and even above 10 GHz, and the emergence of ultra-wide frequency band ultra-high frequency absorption materials that can be widely used in the region above 1 GHz and below 1 THz is highly anticipated. As an example of a magnetic material for high frequency use to date, a rare earth-iron-nitrogen magnetic material having a ferrite-based magnetic material coated on the surface of the powder is known (Patent Document 1).

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: International Publication No. 2008 / 136391 Summary of the invention

[0007] Problems to be solved by the invention

[0008] However, the material disclosed in Patent Document 1 is not efficient enough when applied to magnetic field amplification materials in the above-mentioned region from 1 MHz to 1 THz, and has the problem of not having high-frequency characteristics that can meet the requirements of ultra-wide frequency band absorption materials in the ultra-high frequency region.

[0009] An object of the present disclosure is to provide a magnetic powder having excellent high-frequency characteristics, which has low iron loss and excellent efficiency even when a high frequency is applied, and a method for producing the same.

[0010] Solutions to the problem

[0011] One embodiment of the present invention relates to an α-Fe-containing rare earth-iron-nitrogen magnetic powder having a core region and an α-Fe-containing region outside the above-mentioned core region, wherein the core region contains rare earth R (R is at least one selected from Y, Ce, Pr, Nd, Gd, Tb, Dy, Ho, Er, Tm, Lu and Sm, and when Sm is contained, Sm is less than 50 atomic% relative to the whole R component), Fe and N, and the α-Fe-containing region contains α-Fe and at least one selected from the oxides, nitrides and oxynitrides of the above-mentioned rare earth R.

[0012] In addition, one embodiment of the present invention involves an α-Fe-containing rare earth-iron-nitrogen magnetic powder having a core region and an α-Fe-containing region outside the above-mentioned core region, wherein the core region contains rare earth R (R is at least one selected from Y, Ce, Pr, Nd, Gd, Tb, Dy, Ho, Er, Tm, Lu and Sm, and when Sm is contained, Sm is less than 50 atomic% relative to the whole R component), Fe, and N, and the α-Fe-containing region has a sea-island structure including a sea region and an island region, the atomic concentration (%) of Fe in the island region is higher than that in the sea region, and the atomic concentration (%) of rare earth R and O in the island region is lower than that in the sea region.

[0013] In addition, one embodiment of the present disclosure relates to a method for producing an α-Fe-containing rare earth-iron-nitrogen magnetic powder, which includes a phosphorus treatment step and an oxidation step, wherein the phosphorus treatment step forms a phosphorus compound coating on the rare earth-iron-nitrogen magnetic powder by adding an inorganic acid to a slurry containing rare earth-iron-nitrogen magnetic powder, water, and a phosphorus-containing substance, thereby obtaining a rare earth-iron-nitrogen magnetic powder having a phosphorus compound coating, wherein the rare earth-iron-nitrogen magnetic powder contains rare earth R (R is at least one selected from Y, Ce, Pr, Nd, Gd, Tb, Dy, Ho, Er, Tm, Lu, and Sm, and when Sm is contained, Sm is less than 50 atomic % relative to the entire R component), Fe, and N; and the oxidation step heat treats the rare earth-iron-nitrogen magnetic powder having the phosphorus compound coating at a temperature of 350° C. to 600° C. in an oxygen-containing atmosphere.

[0014] Effects of the Invention

[0015] According to the present disclosure, it is possible to provide a magnetic powder having excellent high-frequency characteristics, low iron loss and excellent efficiency even when a high frequency is applied, and a method for producing the same. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 The XRD analysis results of the magnetic powders prepared in Examples 1 to 4 and Comparative Examples 1 to 3 are shown.

[0017] Figure 2A A STEM image and a STEM-EDX image of the vicinity of the surface of the cross section of the magnetic powder produced in Comparative Example 1 are shown.

[0018] Figure 2B The line analysis results of the vicinity of the surface of the cross section of the magnetic powder produced in Comparative Example 1 are shown.

[0019] Figure 3A A STEM image and a STEM-EDX image of the surface vicinity of a cross section of the magnetic powder produced in Example 1 are shown.

[0020] Figure 3B The line analysis results of the vicinity of the surface of the cross section of the magnetic powder produced in Example 1 are shown.

[0021] Figure 4A A STEM image and a STEM-EDX image of the surface vicinity of a cross section of the magnetic powder produced in Example 2 are shown.

[0022] Figure 4B The line analysis results of the vicinity of the surface of the cross section of the magnetic powder produced in Example 2 are shown.

[0023] Figure 5AA STEM image of the entire α-Fe-containing region in the cross section of the magnetic powder produced in Example 2 is shown.

[0024] Figure 5B The line analysis results of the entire α-Fe-containing region of the cross section of the magnetic powder produced in Example 2 are shown.

[0025] Fig. 6A A STEM image and a STEM-EDX image of the surface vicinity of a cross section of the magnetic powder produced in Example 4 are shown.

[0026] Figure 6B The line analysis results of the vicinity of the surface of the cross section of the magnetic powder produced in Example 4 are shown.

[0027] Fig. 7A A STEM-EDX image of the entire α-Fe-containing region in the cross section of the magnetic powder produced in Example 4 is shown.

[0028] Figure 7B The line analysis results of the entire α-Fe-containing region of the cross section of the magnetic powder produced in Example 4 are shown.

[0029] Figure 8 A TEM image of the entire α-Fe-containing region in the cross section of the magnetic powder produced in Example 4 and an electron diffraction pattern are shown.

[0030] Fig. 9 The frequency dependence of the complex relative permeability of the magnetic materials using the magnetic powders prepared in Examples 1 to 4 and Comparative Examples 1 to 3 is shown.

[0031] Fig.10 Shows Figure 3A An enlarged view of the surface vicinity of a cross section of the magnetic powder of Example 1 is shown.

[0032] Fig.11 The frequency dependency of the complex relative magnetic permeability of the magnetic material using the magnetic powder produced in Example 6 is shown. DETAILED DESCRIPTION

[0033] Hereinafter, the embodiments of the present disclosure are described in detail. Among them, the embodiments shown below are examples for concretizing the technical ideas of the present disclosure, and the present disclosure is not limited by the following contents. It should be noted that in this specification, the term "process" is not only an independent process, but also is included in this term as long as the intended purpose of the process can be achieved when it cannot be clearly distinguished from other processes. In addition, the numerical range shown using "~" indicates a range in which the numerical values ​​recorded before and after the "~" are respectively the minimum and maximum values.

[0034] In this specification, "high frequency" refers to electromagnetic waves with high frequency, and in this disclosure, unless otherwise specified, it specifically refers to electromagnetic waves above 1 MHz and below 1 GHz. In addition, "ultra-high frequency" refers to electromagnetic waves with a frequency higher than "high frequency", above 1 GHz and below 1 THz.

[0035] In this specification, "excellent efficiency" means that at a certain frequency f, the ratio of the imaginary term (μ") of the complex relative permeability (μ) of the magnetic material to the real term (μ'), that is, tanδ=μ" / μ' (also called loss coefficient) takes a small value. δ is called the phase difference. In addition, the value of (90°-δ) is called the phase angle θ. Therefore, "excellent efficiency" means that, in contrast to δ, θ takes a large value and is close to 90°. By making tanδ and δ small, or θ large and close to 90°, it is possible to amplify while reducing the loss of electromagnetic waves of frequency f. In the magnetic field amplification characteristics, an increase in the value of θ (a decrease in the values ​​of tanδ and δ) is referred to as "an improvement in θ (tanδ)", and on the other hand, a decrease in the value of θ (an increase in the values ​​of tanδ and δ) is referred to as "a deterioration in θ (tanδ)" in the magnetic field amplification characteristics.

[0036] In this specification, the "magnetic field amplification" property refers to the fact that the real term (μ') of the complex relative permeability of the magnetic material is greater than 1, which is the real term of the relative permeability in a vacuum. This is a property that increases the magnetic field in the space where the magnetic material is placed compared to the vacuum (or atmosphere). Good or high magnetic field amplification characteristics refer to high μ', and materials with μ' greater than 2 at a certain frequency f are referred to as "magnetic field amplification magnetic materials" (at frequency f). When referred to as relative permeability, it is a general term for the absolute value of the real term and the absolute value of the imaginary term of the complex relative permeability. When referred to as high relative permeability, unless otherwise specified, it refers to high real term of relative permeability.

[0037] In this specification, the "ultra-high frequency absorption" characteristic refers to the absorption characteristic in the ultra-high frequency region, which is the characteristic that the imaginary term (μ") of the complex relative permeability of the magnetic material in the ultra-high frequency region is greater than 0, and the high frequency incident on the space where the magnetic material is placed is attenuated. Good or high ultra-high frequency absorption characteristics at a certain frequency f means that μ" is high at the frequency f. In addition, materials in which μ" is greater than 0 in the ultra-high frequency region are referred to as "magnetic materials for ultra-high frequency absorption." Limited to magnetic materials for ultra-high frequency absorption, increasing μ" is also referred to as "μ" improvement, and reducing μ" is also referred to as "μ" deterioration. In addition, the magnetic field amplification characteristics in the high frequency region and the high-frequency absorption characteristics in the ultra-high frequency region are collectively referred to as "high-frequency characteristics."

[0038] <<α-Fe Rare Earth-Iron-Nitrogen Magnetic Powder>>

[0039] The α-Fe-containing rare earth-iron-nitrogen magnetic powder of this embodiment has a core region and an α-Fe-containing region outside the core region, wherein the core region includes rare earth R (R is at least one selected from Y, Ce, Pr, Nd, Gd, Tb, Dy, Ho, Er, Tm, Lu and Sm, and when Sm is included, Sm is less than 50 atomic% relative to the total R component), Fe and N, and the α-Fe-containing region includes α-Fe and at least one selected from oxides, nitrides and oxynitrides of rare earth R.

[0040] <Nuclear Area>

[0041] The core region contains rare earth-iron-nitrogen powder, specifically, the region contains rare earth R (R is at least one selected from Y, Ce, Pr, Nd, Gd, Tb, Dy, Ho, Er, Tm, Lu and Sm, and when Sm is included, Sm is less than 50 atomic % relative to the whole R component), Fe and N. The core region has Th2Zn 17 Type or Th2Ni 17 The crystalline structure of the type may be a structure containing the general formula R x Fe 100-x-y N y R represented by (wherein R is at least one selected from Y, Ce, Pr, Nd, Gd, Tb, Dy, Ho, Er, Tm, Lu, Sm, and when Sm is included, Sm is less than 50 atomic % relative to the entire R component), nitride of iron (Fe) and nitrogen (N). Here, x is 3 to 30, y is 10 to 30, and the remainder is preferably mainly Fe. When Sm is included, Sm is less than 50 atomic %, preferably less than 25 atomic %, and more preferably less than 5 atomic % relative to the entire R component.

[0042] The method for producing the rare earth-iron-nitrogen magnetic powder constituting the core region is not particularly limited, and an example of the production method is described in detail below.

[0043] (Solid Phase Method)

[0044] The method for producing rare earth-iron-nitrogen magnetic powder based on solid phase method includes:

[0045] A step of mixing R oxide powder, Fe raw material and Ca powder (mixing step),

[0046] a step of reducing the obtained mixture (reduction step),

[0047] A step of subjecting the alloy particles obtained in the reduction step to nitriding treatment (nitriding step).

[0048] [Mixing process]

[0049] The mixing step is to obtain alloy particles by mixing rare earth R oxide powder, Fe raw material and Ca powder. In the mixing step, as the Fe raw material, not only metal Fe, but also Fe2O3 and / or Fe3O4 can be used. When using Fe2O3 and / or Fe3O4, the content (the total molar number of Fe contained in Fe2O3 and / or Fe3O4 relative to the total molar number of Fe contained in metal Fe, Fe2O3 and / or Fe3O4) is preferably 30 atomic % or less. Due to the heat of reaction when these iron oxides are reduced by Ca, the overall reaction is uniform, which is conducive to saving external energy and improving the yield. The mixing amount of granular Ca needs to be sufficient to reduce the amount of oxide of R oxide and the selectively mixed metal oxide. The mixing amount of granular Ca can be more than 0.5 times and less than 3 times, preferably more than 1 times and less than 2 times, relative to the oxygen atom equivalent contained in R oxide and selectively mixed Fe2O3 and / or Fe3O4.

[0050] [Reduction process]

[0051] The mixed powder obtained by the mixing process is placed in a heating container that can be vacuum-exhausted. After the heating container is vacuum-exhausted, argon gas is introduced while heating at a temperature of 600°C or more and 1300°C or less, preferably 700°C or more and 1200°C or less, and more preferably 800°C or more and 1100°C or less. When the heating temperature is lower than 600°C, the reduction reaction of the oxide does not proceed. When the heating temperature exceeds 1300°C, rare earths and Fe sometimes melt and become a mass. In addition, when the heating temperature is higher than 700°C, the reduction time can be short, and there is a tendency to improve productivity. When it is set to be lower than 1200°C, the scattering of Ca can be reduced, and there is a tendency to further reduce the deviation during reduction. From the viewpoint of more uniformly carrying out the reduction reaction, the heat treatment time can be less than 4 hours, preferably less than 120 minutes, and more preferably less than 90 minutes. The lower limit of the heat treatment time is preferably more than 10 minutes, and more preferably more than 30 minutes. Here, when the mixed powder contains an appropriate amount of Fe2O3 and / or Fe3O4 in addition to metallic Fe, spontaneous heat is generated during the temperature rise process, and a uniform reaction is carried out efficiently. On the other hand, when Fe2O3 and / or Fe3O4 are mixed in an amount exceeding 30 atomic % relative to metallic Fe in terms of Fe element conversion as in the above-mentioned mixing step, explosion or scattering may sometimes occur due to extremely large heat release. In addition, by controlling the reduction temperature, the particle size of the obtained rare earth-iron-nitrogen magnetic powder can be controlled. Generally speaking, as the reduction temperature increases, the particle size of the powder increases.

[0052] [Nitriding process]

[0053] The nitriding process is a process of nitriding the alloy particles obtained by the reduction process. In argon gas, it is preferably cooled to a temperature range of 250°C to 800°C, more preferably 300°C to 600°C. In order to suppress the decomposition of the nitridation product in the later nitriding process and improve the reaction efficiency, it is further preferably cooled to a temperature range of 400°C to 550°C. Then, the heating container is vacuum evacuated again and nitrogen is introduced. The introduced gas is not limited to nitrogen, and can be a gas containing nitrogen atoms, for example, ammonia. Nitrogen can be introduced at a pressure above atmospheric pressure while heating for several hours. It is preferred to stop heating after about 5 hours of heating and cool naturally.

[0054] The product obtained after the nitriding process includes, in addition to the rare earth-iron-nitrogen magnetic powder, CaO generated as a by-product, unreacted metallic calcium, etc., which sometimes become a sintered mass state composed of them. In this case, as a water washing process, the product can be put into ion exchange water to separate calcium oxide (CaO) and other calcium-containing components from the magnetic powder in the form of a calcium hydroxide (Ca(OH)2) suspension. As this water washing process, stirring, standing, and removing the supernatant in water can be repeated many times. Furthermore, the residual calcium hydroxide can be fully removed by washing the magnetic powder with acetic acid or the like. From the perspective that the residual unreacted Ca becomes calcium nitride (Ca3N2) and makes it easier to remove, it is preferred to perform the water washing process after the heat treatment in a nitrogen atmosphere. The rare earth-iron-nitrogen magnetic powder thus obtained has a tendency for the particle size distribution to become sharper.

[0055] (Precipitation method)

[0056] The method for producing rare earth-iron-nitrogen magnetic powder based on precipitation method includes:

[0057] A step of mixing a solution containing R and Fe with a precipitant to obtain a precipitate containing R and Fe (precipitation step);

[0058] a step of calcining the precipitate to obtain an oxide containing R and Fe (oxidation step);

[0059] A step of heat-treating the oxide in an atmosphere containing a reducing gas to obtain a partial oxide (pretreatment step);

[0060] A step of reducing part of the oxide (reduction step); and

[0061] A step of nitriding the alloy particles obtained in the reduction step (nitriding step).

[0062] [Precipitation process]

[0063] In the precipitation process, a raw material containing rare earth R and a raw material containing iron Fe are dissolved in a strongly acidic solution to prepare a solution containing R and Fe. As the R raw material and the Fe raw material, there is no limitation as long as they can be dissolved in a strongly acidic solution. For example, from the aspect of ease of acquisition, as the R raw material, R oxide can be cited, and as the Fe raw material, ferrous sulfate (FeSO4) can be cited. The concentration of the solution containing R and Fe can be appropriately adjusted within the range that the R raw material and the Fe raw material are substantially dissolved in the acidic solution. As the acidic solution, sulfuric acid can be cited from the aspect of solubility.

[0064] By reacting a solution containing R and Fe with a precipitant, an insoluble precipitate containing R and Fe can be obtained. Here, the solution containing R and Fe can be a solution containing R and Fe when reacting with the precipitant. For example, the raw material containing R and the raw material containing Fe can be prepared as respective solutions, and the respective solutions can be added dropwise to react with the precipitant. When preparing the respective solutions, it is also possible to appropriately adjust within the range that each raw material is substantially dissolved in the acidic solution. As the precipitant, it is not limited as long as it can react with the solution containing R and Fe in an alkaline solution to obtain a precipitate. Examples include ammonia water, sodium hydroxide, etc., preferably sodium hydroxide.

[0065] After the precipitate is separated, the precipitate is redissolved in the residual solvent in the subsequent heat treatment of the oxidation step. In order to suppress the precipitate from agglomerating when the solvent evaporates, or changes in the particle size distribution, powder particle size, etc., the separated product is preferably desolvated in advance. As a method for desolvation, specifically, when water is used as a solvent, a method of drying in an oven at 70° C. to 200° C. for 5 hours to 12 hours can be cited.

[0066] The precipitation step may include a step of separating and washing the obtained precipitate. The washing step is appropriately performed until the conductivity of the supernatant reaches 5 mS / m or less. As a step of separating the precipitate, for example, a solvent (preferably water) may be added to the obtained precipitate and mixed, and then a filtration method, a decantation method, etc. may be used.

[0067] [Oxidation process]

[0068] The oxidation process refers to a process of obtaining an oxide containing R and Fe by calcining the precipitate formed in the precipitation process. For example, the precipitate can be converted into an oxide by heat treatment. When the precipitate is heat treated, it needs to be carried out in the presence of oxygen, for example, it can be carried out in an atmospheric atmosphere. In addition, since it must be in the presence of oxygen, it is preferred that the non-metallic part in the precipitate contains oxygen atoms. The heat treatment temperature in the oxidation process (hereinafter referred to as the oxidation temperature) is not particularly limited, and is preferably 700°C or more and 1300°C or less, and more preferably 900°C or more and 1200°C or less. When it is lower than 700°C, the oxidation becomes insufficient, and when it exceeds 1300°C, there is a tendency that the shape, average particle size and particle size distribution of the target rare earth-iron-nitrogen magnetic powder cannot be obtained. The heat treatment time is also not particularly limited, and can be 0.5 hours or more and 4 hours or less, and preferably 1 hour or more and 3 hours or less.

[0069] [Pre-treatment process]

[0070] The pretreatment step is a step of obtaining a partial oxide in which a part of the oxide is reduced by heat-treating the oxide containing R and Fe in an atmosphere containing a reducing gas.

[0071] [Reduction process]

[0072] The reduction process refers to a process of obtaining alloy particles by heating part of the oxide at 600°C or more and 1300°C or less, preferably 700°C or more and 1200°C or less, and more preferably 800°C or more and 1100°C or less in the presence of a reducing agent. When the heating temperature is lower than 600°C, the reduction reaction of the oxide does not proceed. When the heating temperature exceeds 1300°C, R and Fe sometimes melt and become a mass. In addition, when the heating temperature is higher than 700°C, the reduction time can be shortened, and there is a tendency to improve productivity. When the heating temperature is lower than 1200°C, the scattering of Ca as a reducing agent can be reduced, and there is a tendency to further reduce the deviation during reduction. By controlling the reduction temperature, the particle size of the rare earth-iron-nitrogen magnetic powder can be controlled. Generally speaking, as the reduction temperature increases, the particle size of the powder increases. From the perspective of making the reduction reaction more uniform, the heat treatment time is preferably less than 120 minutes, more preferably less than 90 minutes, and the lower limit of the heat treatment time is preferably more than 10 minutes, more preferably more than 30 minutes.

[0073] [Nitriding process]

[0074] The nitriding step is a step of obtaining anisotropic magnetic powder by nitriding the alloy particles obtained in the reduction step. Since the granular precipitate obtained in the precipitation step is used, porous block-shaped alloy particles can be obtained in the reduction step. As a result, heat treatment and nitriding can be performed directly in a nitrogen atmosphere without pulverization, so nitriding can be performed uniformly.

[0075] The heat treatment temperature in the nitriding treatment of the alloy particles (hereinafter referred to as the nitriding temperature) is preferably 250°C to 800°C, more preferably 300°C to 600°C. In addition, in order to suppress the decomposition of the nitriding product in the subsequent nitriding step and improve the reaction efficiency, it is particularly preferred to set the temperature to 400°C to 550°C, and replace the atmosphere with a nitrogen atmosphere in this temperature range. The heat treatment time may be set to a degree that the nitriding of the alloy particles can be fully and uniformly performed.

[0076] <α-Fe containing region>

[0077] The α-Fe-containing region exists outside the core region. The α-Fe-containing region contains α-Fe and at least one selected from oxides, nitrides, and oxynitrides of rare earth R. The α-Fe-containing region preferably contains oxides or oxynitrides of rare earth R. For example, when rare earth R is Nd, the oxides, nitrides, and oxynitrides of rare earth R are neodymium oxide, neodymium nitride, and neodymium oxynitride, respectively. The α-Fe-containing region further improves tanδ and phase angle θ in the high-frequency region by improving the insulation between adjacent magnetic particles and reducing the iron loss caused by eddy currents across the particles, thereby obtaining a more efficient magnetic material for magnetic field amplification. Without damaging the magnetic coupling, the α-Fe-containing region may also further contain composite oxides, composite nitrides, composite oxynitrides, etc. containing rare earth R and iron. These composite oxides, composite nitrides, and composite oxynitrides may also have a perovskite structure or a spinel structure. In addition, since the α-Fe-containing region reduces demagnetization by magnetically coupling adjacent magnetic grains, the real term μ' of the magnetic permeability of the magnetic field amplifying magnetic material tends to further increase.

[0078] The α-Fe-containing region preferably includes at least one nanocrystal selected from oxides, nitrides, and nitrogen oxides of rare earth R, and nanocrystals containing α-Fe. By including these nanocrystals, it can be considered that the effects of electrical insulation and magnetic coupling become greater. The "electrical insulation" mentioned here means that due to the presence of a high-resistance α-Fe-containing region on the surface of the magnetic powder, the conduction between the core regions of adjacent magnetic particles is cut off, thereby preventing the generation of eddy currents across the core regions. The eddy current loss caused by electrical insulation is suppressed to achieve "excellent efficiency". In addition, the "magnetic coupling" mentioned here means that due to the presence of a high-resistance but strongly magnetic α-Fe-containing region on the surface of the magnetic powder, strong magnetic coupling and static magnetoelectric coupling are generated between adjacent core regions. Since the magnetic coupling reduces local demagnetization, the demagnetization acting on the core region becomes weaker, so that a high relative magnetic permeability can be achieved. In order to achieve the above-mentioned effect, the α-Fe-containing region is preferably present as an α-Fe-containing region layer outside the core region.

[0079] The nanocrystals include at least one of oxides, nitrides, and oxynitrides selected from rare earth R contained in the α-Fe region, and the average particle size of the nanocrystals is preferably 1 nm or more and less than 1000 nm, more preferably 1 nm or more and less than 100 nm, further preferably 1 nm or more and less than 20 nm, and particularly preferably 1 nm or more and less than 10 nm. The average particle size of the nanocrystals containing α-Fe is preferably 1 nm or more and less than 1000 nm, more preferably 1 nm or more and less than 100 nm, further preferably 1 nm or more and less than 20 nm, and particularly preferably 1 nm or more and less than 10 nm. The particle size of these nanocrystals can be measured by TEM (transmission electron microscopy), STEM (scanning transmission electron microscopy), or EDX (energy dispersive X-ray analysis) of the cross-section of the α-Fe rare earth-iron-nitrogen magnetic powder.

[0080] In addition, when the crystallite diameter is greater than 1 nm and less than 100 nm, the crystallite diameter of the nanocrystal containing α-Fe can be calculated by the following method: using the half-value width of the peak of the (110) plane measured by powder X-ray diffraction method, according to the Scherrer formula D=Kλ / βcosθ (K: Scherrer constant 0.9, λ: X-ray wavelength (nm), β: half-value width of the diffraction peak (radian), θ: diffraction angle (radian)). For example, the half-value width of the nanocrystal containing α-Fe can be obtained by measuring at a step size of 2θ=0.02 between 10<2θ<90 under an X-ray source CuKα, 40kV, and 20mA. For example, λ uses a value measured at a wavelength of 0.154nm.

[0081] In terms of the α-Fe-containing region as a whole, the atomic concentration of Fe (atomic %) is preferably 25% or more, more preferably 50% or more. The upper limit of the atomic concentration of Fe is not particularly limited, and may be 80% or less. When the atomic concentration of Fe is 25% or more, magnetic coupling can be ensured, and there is a tendency for demagnetization to decrease and magnetic permeability to increase.

[0082] For the entire α-Fe-containing region, the atomic concentration (atomic %) of rare earth R is preferably 2% or more and 50% or less, more preferably 5% or more and 30% or less. In the entire α-Fe-containing region, the atomic concentration (atomic %) of nitrogen is preferably 0% or more and 50% or less, more preferably 0.01% or more and 30% or less. For the entire α-Fe-containing region, the atomic concentration (atomic %) of oxygen is preferably 0% or more and 55% or less, more preferably 0.01% or more and 30% or less. The atomic concentration of each element in the α-Fe-containing region can be obtained by averaging the atomic concentration in each region of the STEM-EDX line analysis.

[0083] The average atomic concentration (atomic %) of O in the entire α-Fe region is preferably higher than the average atomic concentration (atomic %) of O in the core region. The average atomic concentration of O in the α-Fe region is preferably 1.05 times or more of the average atomic concentration of O in the core region, more preferably 1.5 times or more, further preferably 2 times or more, and particularly preferably 4 times or more. In addition, the average atomic concentration of R in the α-Fe region is less than 2 times, preferably 1.9 times or less, and more preferably 1.8 times or less of the average atomic concentration of R in the core region. The average atomic concentration of R in the α-Fe region can be more than 0.1 times, preferably 0.5 times or more of the average atomic concentration of R in the core region. The "average atomic concentration" of a specific element here refers to the STEM-EDX line analysis of one or more line segments in the thickness direction from the core region to the outermost surface of the α-Fe region in the α-Fe rare earth-iron-nitrogen magnetic powder, and the measured values ​​of the atomic concentration of element X at more than 50 points are obtained, and the atomic concentration after averaging is obtained.

[0084] The thickness of the α-Fe-containing region is preferably 0.01% or more and less than 50% of the average particle size of the α-Fe-containing rare earth-iron-nitrogen magnetic powder, more preferably 0.01% or more and less than 45%, further preferably 0.01% or more and less than 35%, and particularly preferably 0.5% or more and less than 20%. By setting it to 0.001% or more, there is a tendency for electrical insulation to be improved. When it is less than 50%, μ' has a tendency to become larger due to the presence of the core region containing rare earth R, Fe, and N.

[0085] The thickness of the α-Fe-containing region is preferably greater than 1 nm and less than 10 μm, more preferably greater than 10 nm and less than 5 μm. In addition, from the viewpoint of improving μ' in the high-frequency region, it is further preferably greater than 50 nm and less than 1 μm. By being greater than 1 nm, there is a tendency for improved electrical insulation. When it is less than 10 μm, μ' tends to increase due to the presence of the core region. The thickness of the α-Fe-containing region can be measured by the following method: in the TEM, STEM or FE-SEM observation image of the cross-section of the α-Fe-containing rare earth-iron-nitrogen magnetic powder, a composition analysis is performed by line analysis or surface analysis based on a TEM image and a secondary electron / reflected electron image or EDX, and further by point analysis with a sufficient number of measurement points.

[0086] The surface coverage of the core region containing α-Fe is preferably 10% or more, more preferably 50% or more, further preferably 80% or more, and particularly preferably 100%. By increasing the surface coverage of the core region, it is possible to improve electrical insulation and increase tanδ and phase angle θ. In particular, when the surface coverage is 100%, the electrical isolation of the magnetic powder is further promoted, which can further improve the above effect. The surface coverage of the core region containing α-Fe can be measured by observing the cross section of the powder using TEM, STEM or FE-SEM equipped with EDX, and the ratio of the length of the contact portion between the α-Fe region and the core region to the entire perimeter of the observed core region is defined as "surface coverage". At this time, it is preferred to measure the cross sections of 20 to 50 magnetic powders in the observed image by the above method, and the average value is used as the surface coverage.

[0087] In the α-Fe-containing rare earth-iron-nitrogen magnetic powder, the core region contains a rare earth-iron-nitrogen compound, and in the XRD diffraction pattern, the ratio (I) / (II) of the diffraction peak intensity (I) of the (110) plane of α-Fe and the peak intensity (II) of the strongest line of the rare earth-iron-nitrogen compound in the core region is preferably 0.01 or more and less than 10, more preferably 0.02 or more and less than 5, and more preferably 0.1 or more and less than 2. The diffraction peak intensity (I) of the (110) plane of α-Fe represents the amount of α-Fe present, and when the above ratio (I) / (II) is 0.01 or more and less than 10, there is a tendency to achieve both magnetic coupling and electrical insulation between magnetic particles. When the ratio (I) / (II) is 0.01 or more, the electrical insulation is improved by the α-Fe separation phase having a specific thickness, and there is a tendency to increase μ'. When the ratio (I) / (II) is lower than 10, electrical insulation improves, the volume fraction of the core region increases, and therefore μ' tends to increase. It should be noted that the diffraction peak intensity in the XRD diffraction pattern can be obtained by the following method: using a powder X-ray crystal diffraction device for measurement, the measured diffraction peak intensity of the (110) plane of α-Fe is divided by the peak intensity of the strongest line of the rare earth-iron-nitrogen compound constituting the core region. For example, it can be obtained by measuring under the conditions of X-ray source CuKα, 40kV, and 20mA between 10<2θ<90 with a step size of 2θ=0.02. The strongest line of the rare earth-iron-nitrogen compound is in Th2Zn 17 In the case of rhombohedral crystal system, the (303) plane is used. 17 In the case of hexagonal crystal (hexagonal system), it is the (302) plane.

[0088] The α-Fe-containing region may have a structure in which nanocrystals of a ferromagnetic α-Fe phase are isolated in an R nitride phase, which is the so-called sea (R nitride phase) - island (nano α-Fe phase) structure. Here, a substance selected from oxides, nitrides, and nitrides of α-Fe and rare earth R is referred to as R nitride. Since the α-Fe-containing region has a sea (R nitride phase) - island (nano α-Fe phase) structure, the α-Fe metal phases are isolated in the R nitride matrix phase as the "sea", and no electroosmosis occurs and electrical insulation is maintained.

[0089] In addition, the α-Fe phase in the α-Fe-containing region can be arranged regularly. When the α-Fe phase in the α-Fe-containing region is arranged regularly, the α-Fe phase is composed of nanocrystalline particles and can be arranged regularly at a high density. Due to the strong magnetic coupling or static magneto-coupling of each α-Fe phase, the magnetic flux is more likely to penetrate the α-Fe-containing region, so the magnetic coupling tends to be more stable.

[0090] In addition, the α-Fe-containing region has a sea-island structure including a sea region and an island region, and may have the following structure: the atomic concentration (%) of Fe in the island region is higher than that in the sea region, and the atomic concentration (%) of rare earths R and O in the island region is lower than that in the sea region. The atomic concentration (%) of Fe in the island region is preferably 10 percentage points higher than the atomic concentration (%) of Fe in the sea region, and more preferably 20 percentage points higher. The atomic concentration (%) of rare earths R and O in the sea region is preferably 2 percentage points higher than the atomic concentration (%) of rare earths R and O in the island region, respectively, and more preferably 5 percentage points higher. The atomic concentration (%) of each element in the island region and the sea region can be obtained by averaging the atomic concentration in each region in the STEM-EDX line analysis.

[0091] The α-Fe-containing rare earth-iron-nitrogen magnetic powder may have the following characteristics when measuring XRD. In the α-Fe-containing rare earth-iron-nitrogen magnetic powder, due to the lattice matching of the α-Fe phase and the R nitride phase, the diffraction peak intensity of the R nitride is also added to the α-Fe (110) plane diffraction peak intensity, so the detected α-Fe (110) plane diffraction peak intensity appears to be stronger than the peak intensity expected when the α-Fe phase and the R nitride phase do not have a lattice match. The size of the oriented crystalline phase is preferably 1 to 100% of the film thickness of the α-Fe region, more preferably 10 to 100%. When it is less than 1%, the effect of magnetic coupling becomes smaller. The larger the volume fraction of the oriented region relative to the α-Fe region, the better, preferably 1 to 100%, more preferably 10 to 100%. When it is 1% or more, there is a situation where the enhancement effect of magnetic coupling becomes greater than when there is no orientation.

[0092] The presence, size and volume fraction of the oriented crystalline phase can be determined by observing the STEM image of the α-Fe rare earth-iron-nitrogen magnetic powder, the ED (electron beam diffraction) device attached to the TEM device, etc. For example, in the cross-sectional STEM photo of the α-Fe rare earth-iron-nitrogen magnetic powder, the region containing both the α-Fe phase and the R nitride phase and having lattice fringes in one direction is regarded as the "oriented region" and image analysis is performed. Using a scanning transmission electron microscope (STEM), five locations of the region containing the α-Fe region of the α-Fe rare earth-iron-nitrogen magnetic powder (when the α-Fe region is thick, it can be divided into multiple fields of view) are photographed, and by comparing the "oriented region" and the non-oriented region in the photographed region, the size and volume fraction of the oriented crystalline phase can be confirmed. In addition, the electron diffraction image of the STEM-ED image can confirm the presence of oriented crystals.

[0093] <Phosphorus Compound Coating>

[0094] The α-Fe-containing rare earth-iron-nitrogen magnetic powder preferably further has a phosphorus compound coating portion. The phosphorus compound coating portion is preferably present outside the α-Fe-containing region, that is, on the opposite side of the core region across the α-Fe-containing region.

[0095] From the viewpoint of improving tanδ and phase angle θ of the magnetic material in the high frequency region and μ" in the ultra-high frequency region, the thickness of the phosphorus compound coating is preferably 1 nm or more and 200 nm or less, and more preferably 2 nm or more and 50 nm or less. It should be noted that the thickness of the coating can be measured as follows: for a cross section of the α-Fe-containing rare earth-iron-nitrogen-based magnetic powder, line analysis or surface analysis is performed by EDX based on TEM, STEM or FE-SEM observation images, and further point analysis with a sufficient number of measurement points is performed to perform composition analysis. . It should be noted that when measured by line analysis or the like, for example, the observed range in which the atomic concentration of phosphorus (P) is 1 atomic % or more can be regarded as the phosphorus compound coating. As an example, a structure can be cited in which the phosphorus compound coating completely covers the surface of the α-Fe rare earth-iron-nitrogen magnetic powder (surface coverage 100%). At this time, it can be considered that the adjacent magnetic particles are in a state of complete electrical insulation. That is, if it is this structure, the phosphorus compound coating has the effect of reducing the iron loss caused by the eddy current across the particles, and further improves tanδ in the high-frequency region. , phase angle θ, thereby obtaining a more efficient magnetic material for magnetic field amplification. In addition, the influence of eddy currents can be reduced up to the ultra-high frequency region, thereby being used as an ultra-high frequency absorption magnetic material that maintains higher ultra-high frequency absorption characteristics. It should be noted that the phosphorus compound coating portion may not completely cover the surface of the α-Fe rare earth-iron-nitrogen magnetic powder. As long as the surface coverage is 10% or more, a certain degree of eddy current reduction effect can be expected. The desired surface coverage is preferably 50% or more, more preferably 80% or more. For a surface of 10% or more and less than 80% In terms of coverage, it is preferred that the detached phosphorus compound exists between the magnetic powders. The surface coverage of the magnetic powder based on the phosphorus compound coating can be estimated by observing the cross section of the powder using TEM, STEM or FE-SEM equipped with EDX, and the ratio of the contact portion length of the phosphorus-containing coating to the entire perimeter of the observed surface of the α-Fe-containing rare earth-iron-nitrogen magnetic powder is defined as the "surface coverage". In this case, it is preferred to measure the cross sections of 20 to 50 magnetic powders in the image observed by the above method, and the average value is used as the surface coverage.

[0096] As the phosphorus compound constituting the phosphorus compound coating, there can be mentioned: inorganic phosphoric acids such as orthophosphoric acid, pyrophosphoric acid, and polyphosphoric acid, and phosphate compounds such as phosphates thereof with Na, Ca, Pb, Zn, Fe, R, ammonium, Mo, W, V, Cr (in the present disclosure, these metal elements and atomic groups are referred to as M components, and may sometimes be simply referred to as M), and "phosphorus-containing amorphous compounds" and "phosphorus-containing nanocrystalline compounds" containing at least one selected from R, Fe, M and N, and P and / or phosphorus-containing substances. Among them, from the viewpoint of making the surface coating of the powder composed of the core region and the α-Fe-containing region dense, phosphates, "phosphorus-containing amorphous compounds" and "phosphorus-containing nanocrystalline compounds" are preferred. The above-mentioned "phosphorus-containing nanocrystalline substances" are rare earth phosphates, or may be in a eutectic or mixed crystal state containing at least one selected from iron phosphate and M phosphate and rare earth phosphates. When "phosphorus-containing nanocrystalline compounds" are included, the thermal stability becomes further improved. Even when the phosphorus-treated bonded magnetic material is produced, after a high-heat kneading process and a heat curing process, the high-frequency characteristics of the magnetic powder tend to be difficult to deteriorate, thereby further contributing to the high thermal stability and excellent efficiency of the final molded body. Here, nanocrystals refer to fine crystals of more than 1 nm and less than 1 μm, and phosphorus compounds containing fine crystals less than 1 nm are also within the scope of amorphous compounds. The crystallinity of the phosphorus compound coating and the diameter of the microcrystals in the phosphorus compound coating can be confirmed by the following methods: lattice image observation based on the TEM method and analysis based on the ED (electron beam diffraction) device attached to the TEM device.

[0097] The content of phosphorus compounds in the α-Fe-containing rare earth-iron-nitrogen magnetic powder is preferably 0.5% by mass or more and 4.5% by mass or less, more preferably 0.55% by mass or more and 2.5% by mass or less, and most preferably 0.75% by mass or more and 2% by mass or less. When it is 4.5% by mass or less, the agglomeration of the rare earth-iron-nitrogen magnetic powder can be reduced, and while suppressing the decrease in relative magnetic permeability, it also has a tendency to reduce the deterioration of tanδ and phase angle θ in the high-frequency region. When it is 0.5% by mass or more, the electrical insulation of the phosphorus compound coating is further improved, and the decrease in relative magnetic permeability can be suppressed in the same way, and there is a tendency to reduce the deterioration of tanδ and phase angle θ in the high-frequency region.

[0098] In addition, the content of phosphorus (P) element in the α-Fe rare earth-iron-nitrogen magnetic powder is preferably 0.02 mass % or more, more preferably 0.05 mass % or more, and further preferably 0.15 mass % or more. The content of phosphorus in the α-Fe rare earth-iron-nitrogen magnetic powder is preferably 4 mass % or less, more preferably 2 mass % or less, and further preferably 1 mass % or less.

[0099] From the point of view of not causing the decrease in efficiency caused by eddy currents, that is, the deterioration of tanδ and phase angle θ, the phosphorus compound preferably coats the surface of at least a portion of the powder containing the core region and the α-Fe region. For magnetic powders, if the surface coverage is 10% or more, it has the effect of reducing eddy currents to a certain extent, but the surface coverage is preferably 50% or more, and more preferably 80% or more. When the surface coverage is 10% or more, the eddy currents generated between the particles are suppressed, and there is a tendency to reduce the deterioration of tanδ and phase angle θ. Based on the phosphorus compound coating, the tanδ and phase angle θ of the α-Fe rare earth-iron-nitrogen magnetic powder containing 100% coverage are extremely deteriorated. According to the composition, crystal structure and powder particle size of the magnetic powder, tanδ below 0.01 and high θ can be achieved at 2MHz.

[0100] From the viewpoint of not causing a decrease in relative magnetic permeability due to eddy currents, in particular a decrease in μ", that is, a deterioration in ultra-high frequency absorption characteristics, the phosphorus compound preferably coats at least a portion of the surface of the powder composed of a core region and an α-Fe-containing region. If the surface coverage is 10% or more, it has the effect of reducing eddy currents to a certain extent, but the surface coverage is preferably 50% or more, and more preferably 80% or more. When the surface coverage is less than 10%, the eddy currents generated between the particles cannot be fully prevented, and μ" tends to decrease based on the skin effect. Based on the phosphorus compound coating, the decrease in relative magnetic permeability of α-Fe-containing rare earth-iron-nitrogen magnetic powder with a coverage of 100% due to eddy currents is extremely small, and depending on the composition, crystal structure and powder particle size of the magnetic powder, a μ" of 1 or more can be achieved at 1 GHz.

[0101] The phosphorus compound coating present on the surface of the α-Fe-containing rare earth-iron-nitrogen magnetic powder may have a region (R high concentration region) in which the rare earth (R) atom concentration is higher than the R atom concentration in the rare earth-iron-nitrogen magnetic powder (core region) as the base material. The R atom concentration in the R high concentration region may be 1.05 times or more of the R atom concentration in the core region, preferably 1.1 times or more, more preferably 1.2 times or more, and further preferably 1.5 times or more. In addition, the R atom concentration in the R high concentration region may be, for example, 4 times or less of the R atom concentration in the core region. Here, the R high concentration region includes: a layer showing the maximum peak of P (phosphorus) in the STEM-EDX line analysis of the α-Fe-containing rare earth-iron-nitrogen magnetic powder. The thickness of the R high concentration region may be, for example, 1 nm or more, preferably 3 nm or more and 150 nm or less, and more preferably 5 nm or more and 100 nm or less. Relative to the R atomic concentration in the core region, the R atomic concentration in the R high concentration region is within the above range, and the resistivity becomes high, and there is a tendency to improve the relative magnetic permeability. The atomic concentration (atomic %) of each element in the R high concentration region can be obtained by the following method: averaging the atomic concentration in the phosphorus compound coating portion in the STEM-EDX line analysis. As a rare earth element, for example, Nd can be used. In this case, as an Nd high concentration region, the Nd atomic concentration can be used as a reference for evaluation.

[0102] The R atom concentration in the R high concentration region may be 0.3 times or more, preferably 1 times or more, of the Fe atom concentration in the R high concentration region. The R atom concentration in the R high concentration region is preferably 20 times or less of the Fe atom concentration in the R high concentration region. By making the relationship between the R atom concentration and the Fe atom concentration in the R high concentration region within the above range, the Fe atom concentration near the core region becomes lower, and there is a tendency for the water resistance to be further improved.

[0103] The atomic concentration ratio R / Fe of R and Fe in the R high concentration region may be 0.3 or more, preferably 0.5 or more, and more preferably 1 or more. The upper limit of R / Fe in the R high concentration region may be 100 or less, or 10 or less. In addition, R / Fe in the R high concentration region may have a higher value than R / Fe in the core region. R / Fe in the R high concentration region may be 1 times or more of R / Fe in the core region, preferably 1.5 times or more, more preferably 2 times or more, and further preferably 5 times or more. By making R / Fe in the R high concentration region within the above range, the Fe atomic concentration near the core region becomes lower, and there is a tendency for water resistance to be further improved.

[0104] The α-Fe-containing rare earth-iron-nitrogen magnetic powder may further have a Mo high concentration layer. In the Mo high concentration layer, Mo used when forming the phosphorus compound coating portion exists in a higher concentration than the iron oxide layer and the α-Fe-containing region. The Mo high concentration layer is preferably present outside the α-Fe-containing region. Depending on the situation, by having a Mo high concentration layer, there is an effect of improving the strength of the coating layer and improving corrosion resistance.

[0105] When the α-Fe rare earth-iron-nitrogen magnetic powder contains a Mo high concentration layer, the thickness of the Mo high concentration layer is preferably 0.01% to 10% of the average particle size of the α-Fe rare earth-iron-nitrogen magnetic powder, more preferably 0.02% to 1%. In addition, the thickness of the Mo high concentration layer is preferably 1 nm to 1 μm, more preferably 2 nm to 100 nm.

[0106] The α-Fe-containing rare earth-iron-nitrogen magnetic powder may further have an iron oxide layer. The iron oxide layer is mainly composed of iron oxide containing Fe2O3. The iron oxide layer is preferably present on the outside of the α-Fe-containing region, more preferably on the outside of the phosphorus compound coating, and further preferably on the outside of the Mo high concentration layer. The iron oxide layer has the effect of imparting thermodynamic stability to the α-Fe-containing region and improving electrical insulation.

[0107] When the α-Fe-containing rare earth-iron-nitrogen magnetic powder has an iron oxide layer, the thickness of the iron oxide layer is preferably greater than 0% and less than 20% of the average particle size of the α-Fe-containing rare earth-iron-nitrogen magnetic powder, and more preferably greater than 0.001% and less than 5%. When it is less than 20%, there is a tendency that μ' can be suppressed from decreasing. In addition, the thickness of the iron oxide layer is preferably greater than 0nm and less than 1μm, and more preferably greater than 1nm and less than 100nm. By making the thickness of the iron oxide layer less than 1μm, there is a tendency that μ' can be suppressed from decreasing.

[0108] <Magnetic Powder Particle Size>

[0109] The average particle size of the α-Fe rare earth-iron-nitrogen magnetic powder is preferably 0.1 μm or more and 100 μm or less. As a magnetic material for magnetic field amplification, it is preferably 1 μm or more and 100 μm or less. As a magnetic material for ultra-high frequency absorption, it is preferably 0.1 μm or more and 10 μm or less. As a magnetic material for magnetic field amplification described later, the more preferred particle size range is 3 μm or more and 100 μm or less, and as a magnetic material for ultra-high frequency absorption, the particle size range is 0.1 μm or more and 3 μm or less. When it is less than 1 μm, there is a risk of reducing the real term of relative magnetic permeability in the high frequency region and the imaginary term of relative magnetic permeability in the ultra-high frequency region due to the reduced filling amount of magnetic powder in the molded body. If it is less than 0.1 μm, the specific surface area becomes larger, and there is a situation where the volume fraction of the magnetic body part with high real term of relative magnetic permeability in the high frequency region and imaginary term of relative magnetic permeability in the ultra-high frequency region becomes smaller. As a result, there is a tendency for the characteristics of the magnetic material to become extremely low. When it exceeds 10 μm, the μ" of the molded body tends to decrease, and when it further exceeds 100 μm, this tendency becomes significant. At this time, the average particle size is the median particle size measured under dry conditions using a laser diffraction particle size distribution analyzer. That is, the average particle size of the magnetic powder disclosed in the present invention is represented by D50, and D50 refers to the particle size corresponding to 50% of the cumulative value of the volume-based particle size distribution of the α-Fe rare earth-iron-nitrogen magnetic powder.

[0110] When the particle size of the core region of the Fe-containing rare earth-iron-nitrogen magnetic powder increases, eddy currents begin to be generated in the particles from low frequencies based on the skin effect. Therefore, the larger the particle size, the lower the real term of the relative magnetic permeability from the low frequency region. Therefore, by reducing the particle size of the magnetic powder, there is a tendency to maintain the magnetic field amplification characteristics and ultra-high frequency absorption characteristics at a high level to high frequencies. For example, in the case of Nd2Fe 17For N3, the relationship between the particle size r (μm) of the magnetic powder and the frequency f0 (Hz) at which the real term of the relative magnetic permeability begins to decrease is estimated to be f0 = 1 THz when r is 0.1 μm, f0 = 1 GHz when it is 3 μm, and f0 = 1 MHz when it is 100 μm. Therefore, if the upper limit of the particle size is taken as the core region of the Fe-containing rare earth-iron-nitrogen magnetic powder near it, it is preferred as the magnetic material for magnetic field amplification disclosed in the present invention. On the other hand, as the particle size becomes smaller, the filling amount of the magnetic powder in the molded body becomes smaller and the specific surface area becomes larger. For example, in the case of a phosphorus compound coating with a thickness of 10 nm, if the particle size of the powder is 0.1 μm, the relative magnetic permeability is only reduced by about 50%, and if the particle size is 0.05 μm, the relative magnetic permeability becomes about 6%. Therefore, the lower limit of the core region of the Fe-containing rare earth-iron-nitrogen magnetic powder disclosed in the present invention has nothing to do with the frequency and is about 0.1 μm. Due to the above trade-offs, a particle size range that is more suitable for the target frequency band of the magnetic material is preferred.

[0111] The real term (μ') of the relative magnetic permeability of the α-Fe rare earth-iron-nitrogen magnetic powder at 10 MHz is preferably 6 or more, more preferably 10 or more. When the real term of the relative magnetic permeability at 10 MHz is 6 or more, it can be preferably used as a transformer core. The relative magnetic permeability of the α-Fe rare earth-iron-nitrogen magnetic powder can be measured by the following method: Mix the α-Fe rare earth-iron-nitrogen magnetic powder and epoxy resin so that the mass ratio of the resin and the magnetic powder is 3:97, and prepare a magnetic material for evaluation with a thickness of 1 mm. The prepared magnetic material for evaluation can be evaluated and measured by an impedance analyzer (HP4291B, manufactured by Hewlett-Packard Company). Below, for the evaluation of μ', μ", δ and θ above 1 MHz and below 1 GHz, it can be evaluated by preparing the same magnetic material for evaluation.

[0112] When the phase angle at 100MHz is θ1 and the phase angle at 2MHz is θ2, the θ1 / θ2 of the α-Fe rare earth-iron-nitrogen magnetic powder is preferably greater than 0.8, and more preferably greater than 0.9. The closer θ1 / θ2 is to 1 when it is greater than 0.8, the less energy efficiency can be reduced even at high frequencies. It should be noted that the phase angle θ is the phase angle when μ' (real term of complex relative permeability) and μ" (imaginary term of complex relative permeability) are expressed on a complex plane, and is the phase angle θ that is the complementary angle of δ in tanδ defined above.

[0113] The phase angle θ of the α-Fe rare earth-iron-nitrogen magnetic powder at 13 MHz is preferably 85° or more (tan δ is 0.0875 or less), and more preferably 88° or more (tan δ is 0.0349 or less). When the phase angle θ at 13 MHz is 85° or more, it can be suitably used as an antenna material for RFID.

[0114] It should be noted that the magnetic anisotropy of the core region of the Fe-containing rare earth-iron-nitrogen magnetic powder of the present embodiment shows in-plane crystalline magnetic anisotropy, and the in-plane crystalline magnetic anisotropy has the following property: the magnetic moment is more likely to be oriented in the c-plane direction than in the c-axis direction. The magnetic powder of the present embodiment has this characteristic, which is very important for maintaining a high real term μ' of relative magnetic permeability in the high-frequency region and further presenting a high imaginary term μ" of relative magnetic permeability in the ultra-high frequency region. With respect to the magnetic powder of the present embodiment, the absolute value of the negative crystalline magnetic anisotropy energy is very large. In addition, since the magnetic powder having in-plane crystalline magnetic anisotropy is contained in a non-oriented manner, its natural resonance frequency is widely distributed in the range of more than 1 GHz and less than 1 THz. Therefore, below 1 GHz, an increase in μ" and a decrease in μ' caused by natural resonance do not occur, and in the region of more than 1 GHz and less than 1 THz, a high μ" caused by natural resonance is presented in a wide band. In particular, for the present embodiment, For magnetic powders of this type, the generation of eddy currents between particles can be suppressed by coating the surface of the ferromagnetic powder with phosphorus compounds and α-Fe-containing regions contained in the magnetic powder, or by the presence of phosphorus compounds and iron oxide layers between the magnetic powders. Furthermore, when the magnetic powder is set to a specific average particle size, the generation of eddy currents within the particles can also be suppressed, and the deterioration of the original high-frequency characteristics of the magnetic powder caused by eddy currents is reduced, with a tendency to further improve in the 1MHz~1THz region. "Magnetic materials for magnetic field amplification" made by a material design concept that encompasses such a wide frequency band at once is not yet known. In addition, "ultra-high frequency absorption materials" that function seamlessly in an "ultra-wide frequency band" according to the same design concept are also unknown.

[0115] <<Magnetic materials for magnetic field amplification>>

[0116] The magnetic material for magnetic field amplification of the present embodiment includes α-Fe rare earth-iron-nitrogen magnetic powder. By including α-Fe rare earth-iron-nitrogen magnetic powder, the following excellent efficiency can be achieved: for magnetic field amplification purposes, a high relative magnetic permeability of μ' of 2 or more in the region of 1 MHz to less than 1 GHz is achieved, and a phase angle θ becomes larger in the region of 1 MHz to less than 1 GHz.

[0117] The particle size of the α-Fe rare earth-iron-nitrogen magnetic powder is preferably greater than 1 μm and less than 100 μm. The reason is as described above, because if a powder larger than 100 μm is used as a magnetic material for magnetic field amplification above 1 MHz, there is a tendency for the relative magnetic permeability to decrease due to the skin effect. In addition, when a powder larger than 7 μm is effectively used as a magnetic material for magnetic field amplification, a large pressure of about 0.5 GPa or more is applied to increase the volume fraction, so the powders are in contact with each other, resulting in large eddy current losses, and the real term of the relative magnetic permeability is greatly reduced. Therefore, it is preferred to cover the α-Fe rare earth-iron-nitrogen magnetic powder with a fine and moderately soft material such as a phosphorus compound that is not as strong as ferrites and transition metal oxides and not as overly soft as resins, and sandwich it between the particles, thereby suppressing the deterioration of the relative magnetic permeability and other properties originally possessed by the magnetic powder.

[0118] The magnetic material for magnetic field amplification can be suitably used at a frequency of 1 MHz or more and less than 1 GHz, and can also be used as a magnetic material for ultra-high frequency absorption when it is above 1 GHz. Therefore, depending on the composition, particle size distribution, etc. of the α-Fe rare earth-iron-nitrogen magnetic powder, the imaginary term of the relative magnetic permeability sometimes begins to increase in the frequency region of 0.5 GHz or more and less than 1 GHz. The magnetic material for magnetic field amplification of the present embodiment can be used in the region of 1 MHz or more and less than 0.5 GHz, preferably in the region of 1 MHz or more and less than 0.1 GHz. When used as a magnetic material for magnetic field amplification within the above range, a powder of 3 μm or more and 100 μm or less is used instead of a micro-crushing device such as a jet mill, and magnetic field orientation that reduces production capacity is not required, so it is preferred from the perspective of balancing cost and characteristics.

[0119] More specific uses of magnetic materials for magnetic field amplification include coils for wireless power supply, magnetic field amplification materials for RFID (Radio Frequency Identification) tags, transformers, inductors and reactors for high-frequency circuits exceeding 20MHz, etc. For example, it can be made into a thin sheet and pasted on the back of an antenna or a transceiver to concentrate the magnetic flux inside the sheet by using the magnetic field amplification characteristics; or inserted into a cylindrical or rectangular coil; or a wire is wound around a toroidal core with a yoke to increase the real term of the relative magnetic permeability of the coil, and used as a magnetic material for magnetic field amplification.

[0120] The magnetic material for magnetic field amplification of the present embodiment has a characteristic that the real term of relative magnetic permeability is high even in the high-frequency region. For example, the real term of relative magnetic permeability at a frequency of 1 MHz or more and 20 MHz or less is preferably 3 or more, and more preferably 4 or more. In addition, the real term of relative magnetic permeability at a frequency greater than 20 MHz and less than 1 GHz is preferably 2 or more, and more preferably 3 or more. In addition, for the magnetic material for magnetic field amplification of the present embodiment, for example, the real term μ' of relative magnetic permeability at a frequency of 20 MHz can be 3.2 or more, preferably 3.5 or more, more preferably 4 or more, and more preferably 4.5 or more. The real term μ' of relative magnetic permeability of the magnetic material for magnetic field amplification of the present embodiment at a frequency of 20 MHz can be, for example, set to 200 or less, or 100 or less.

[0121] The magnetic material for magnetic field amplification of the present embodiment has tanδ (μ" / μ') and phase angle θ at 20 MHz of 0.33 or less and 79° or more, preferably 0.29 or less and 80° or more, and more preferably 0.25 or less and 86° or more. In addition, tanδ and phase angle θ at 20 MHz can be 0.0001 or less and 88 or more. When tanδ and phase angle θ at 20 MHz are within the above range, it is preferred because it is an efficient and low-cost magnetic material for magnetic field amplification, especially when used at frequencies near them (e.g., 10 MHz or more and 30 MHz or less). When tanδ (μ" / μ') and phase angle θ are 79° or more, heat generation when introduced into elements and systems can be reduced, and the temperature of components, etc. can be reduced, thereby having a tendency to improve stability. When tanδ and phase angle θ are 0.0001 or less and 89.994 or more, the cost for improving the homogeneity of the material can be reduced. Here, the complex relative magnetic permeability tanδ and the phase angle θ can be measured by the following methods: using an impedance analyzer, a (vector) network analyzer, or a BH analyzer to measure the impedance of the ring-shaped sample and converting the result into the complex relative magnetic permeability, tanδ, and the phase angle θ; using the S parameter method according to the frequency region (for example, when measuring with a network analyzer above 500 MHz).

[0122] In addition, the magnetic material for magnetic field amplification of the present embodiment also has the characteristic that the frequency dependence of the relative magnetic permeability is small. For example, in the application of wireless power supply, power is supplied at a frequency of 13.56 MHz, so a magnetic material with a small change in the real term μ' of the relative magnetic permeability in the range of 2 MHz and below 20 MHz including this frequency can be preferably used because of its excellent efficiency. In addition, there are many materials whose relative magnetic permeability changes greatly even below 5 MHz, and in the application of this frequency region, it is also preferable to use a material whose real term of relative magnetic permeability is stable in the region of 2 MHz and below 20 MHz. In these applications, for materials in which the change in μ' is large in the above-mentioned frequency range, the deviation of μ" from 0 also increases accordingly, and therefore, there is a tendency for tanδ and phase angle θ to deteriorate. The ratio of the real term of the relative permeability at 20 MHz to the real term of the relative permeability at 2 MHz is preferably greater than 0.8, and more preferably greater than 0.9. In addition, the ratio of the real term of the relative permeability at 20 MHz to the real term of the relative permeability at 2 MHz may be less than 1.1. When the ratio of the real term of the relative permeability is greater than 0.8, there is a tendency to reduce the decrease in energy efficiency and reduce the heat release of the equipment into which the magnetic material is introduced. In addition, when the ratio of the real term of the relative permeability is less than 1.1, there is a tendency to facilitate the control of the input and output of the device.

[0123] The magnetic material for magnetic field amplification of the present embodiment may also contain a resin. The composite material of the magnetic material and the resin is called a bonded magnetic material, and the resin contained in the bonded magnetic material may be a thermosetting resin or a thermoplastic resin. As thermoplastic resins, polyphenylene sulfide (PPS), polyetheretherketone (PEEK), liquid crystal polymer (LCP), polyamide (PA), polypropylene (PP), polyethylene (PE), thermoplastic elastomers, etc. may be cited. As thermosetting resins, epoxy resins, phenolic resins, urea resins, melamine resins, guanamine resins, unsaturated polyester resins, vinyl ester resins, diallyl phthalate resins, polyurethane resins, silicone resins, polyimide resins, alkyd resins, furan resins, dicyclopentadiene resins, acrylic resins, allyl carbonate resins, thermosetting elastomers generally referred to as rubber, etc. may be cited.

[0124] The content of the resin contained in the bonded magnetic material is preferably 0.1% by mass or more and 95% by mass or less. By making the content of the resin component 0.1% by mass or more, the impact resistance is further improved, and by making it 95% by mass or less, the extreme reduction of relative permeability and magnetization can be suppressed. In addition, for the bonded magnetic material of this embodiment, in the use that requires high relative permeability and impact resistance, for the same reasons as above, it is further preferably in the range of 0.5% by mass or more and 50% by mass or less, and in the case of being used as a transformer for a high-frequency circuit with excellent efficiency, etc., it is most preferably set to a range of 1% by mass or more and 15% by mass or less. In addition, in order to make the real number term of the relative permeability of the magnetic material for magnetic field amplification of this embodiment particularly high and the absorption characteristics as an ultra-high frequency absorption material particularly good, although it varies somewhat depending on the use, it is also preferably set to 15% by mass or less. Moldings that are not sintered and cured and do not contain resin, such as compressed powders using additives such as volatile organic solvents, are very brittle and are very difficult to apply to the following materials: magnetic materials for magnetic field amplification such as wireless power supply coils and magnetic cores of inductors that are loaded; or ultra-high frequency absorbing materials carried on 5G+ and 6G mobile devices that are frequently transported and subjected to a large amount of impact. In addition, molded bodies that contain a large number of penetrating air layers, such as compressed powders that have been press-molded at a pressure of less than 1.5 GPa, will deteriorate due to oxidation when exposed to temperatures above 50°C for a long time; or they will become extremely brittle and have poor impact resistance, so there is a tendency to be unsuitable for use at high temperatures. Therefore, in the molded bodies for the above-mentioned uses, the content of resin is preferably 0.1% by mass or more and 95% by mass or less, more preferably 0.5% by mass or more and 50% by mass or less, and further preferably 1% by mass or more and 15% by mass or less.

[0125] The resin composite for bonding magnetic materials can be obtained by, for example, mixing and / or kneading α-Fe rare earth-iron-nitrogen magnetic powder and resin at a temperature of 180° C. to 300° C. using a mixer. For example, the α-Fe rare earth-iron-nitrogen magnetic powder and resin can be mixed using a mixer, followed by kneading and extruding using a twin-screw extruder, and the resulting strands can be air-cooled and then cut into a size of several mm using a granulator to obtain a granular resin composite for bonding magnetic materials of the present embodiment.

[0126] The bonded magnetic material of the present embodiment can be manufactured by molding a resin compound using an appropriate molding machine. Specifically, for example, the resin compound melted in the drum of the molding machine can be injection molded in a mold to which a magnetic field is applied so that the easy magnetization axes are aligned (orientation process), thereby obtaining a magnetic field oriented molded bonded magnetic material. In addition, by calendering and hot pressing the granular resin compound, sheet-shaped bonded magnetic material sheets for magnetic field amplification and bonded magnetic material sheets for ultra-high frequency absorption can be produced. By calendering it to a thickness of more than 20 μm and less than 200 μm, a magnetic material for magnetic field amplification with a high real number term of relative magnetic permeability can be made, for example, it can be suitably used as a magnetic material molded body sheet for magnetic field amplification for RFID tags, and can be used as a magnetic material molded body sheet for ultra-high frequency absorption for mobile devices.

[0127] <<Magnetic materials for ultra-high frequency absorption>>

[0128] The ultra-high frequency absorbing magnetic material of this embodiment includes α-Fe rare earth-iron-nitrogen magnetic powder. By including α-Fe rare earth-iron-nitrogen magnetic powder, μ" has an imaginary term of relative magnetic permeability greater than 0 in the region of 1 GHz to 0.11 THz, and can also have excellent absorption characteristics such as μ" having 0.8 or more in the region of 1 GHz to 10 GHz.

[0129] The average particle size of the α-Fe-containing rare earth-iron-nitrogen magnetic powder is preferably greater than 0.1 μm and less than 10 μm. The reason is as described above. If it is an ultra-high frequency region of more than 1 GHz, based on the skin effect, the relative magnetic permeability of powders greater than 3 μm tends to decrease. Therefore, the powder particle size must be as large as possible to be greater than 0.1 μm, and direct contact between magnetic particles must be avoided as much as possible. For example, if you want to use 30 μm rare earth-iron-nitrogen magnetic powder for ultra-high frequency magnetic materials, even if it is crushed to less than 5 μm, the magnetic powders will contact and conduct with each other during molding, and sometimes the average size of the mutually conductive agglomerates reaches 30 μm. In this case, compared with the case of using the powder before crushing, the effect of the particle size on the high-frequency characteristics becomes the same, and the purpose of crushing is lost. In particular, when making magnetic sheets, a molding method that simultaneously applies heat and pressure, such as hot pressing and calendering, is often used. In this case, it is preferred that an insulating film such as a phosphorus compound is closely attached to the surface of the magnetic particles, so that even if the magnetic particles are aggregated in the matrix of the molded body, the magnetic particles are electrically insulated. By using a phosphorus compound that is not as hard as ferrite or transition metal oxides, but is fine and moderately soft, to coat the surface of magnetic powder that is easy to aggregate, heat and pressure can be applied simultaneously to produce a high-density and high relative permeability high-frequency magnetic material.

[0130] The magnetic material for ultrahigh frequency absorption of the present embodiment has a characteristic that the imaginary term μ" of the relative magnetic permeability is high even at ultrahigh frequencies. For example, the imaginary term μ" of the relative magnetic permeability at a frequency of 1 GHz or more and less than 20 GHz is preferably greater than 0.2, and more preferably greater than 0.3. In addition, the imaginary term μ" of the relative magnetic permeability at a frequency of 20 GHz or more and less than 1 THz is preferably greater than 0.01, and further preferably greater than 0.1. In addition, for example, at a frequency of 10 GHz, the imaginary term μ" of the relative magnetic permeability of the magnetic material for ultrahigh frequency absorption of the present embodiment can be greater than 0.3, preferably greater than 0.5, more preferably greater than 0.7, and further preferably greater than 0.9. For the ultrahigh frequency absorption magnetic material of the present embodiment, the imaginary term μ" of the relative magnetic permeability at a frequency of 10 GHz can be set to less than 5 or less than 4. In addition, for example, at a frequency of 0.11 THz, the imaginary term μ" of the relative magnetic permeability of the ultrahigh frequency absorption magnetic material of the present embodiment can be set to greater than 0.01, preferably greater than 0.02, more preferably greater than 0.05, and further preferably greater than 0.1. The imaginary term μ" of the relative magnetic permeability of the ultrahigh frequency absorption magnetic material of the present embodiment at a frequency of 0.11 THz can be set to be less than 2, or less than 1.5. In addition, for the ultrahigh frequency absorption magnetic material of the present embodiment, for example, the ratio of the imaginary term μ" of the relative magnetic permeability at 0.11 THz to the imaginary term μ" of the relative magnetic permeability at a frequency of 10 GHz is preferably greater than 0.01, and more preferably greater than 0.1. For the ultrahigh frequency absorption magnetic material of the present embodiment, the ratio of the imaginary term μ" of the relative magnetic permeability at 0.11 THz to the imaginary term μ" of the relative magnetic permeability at a frequency of 10 GHz is preferably less than 5, and more preferably less than 1. By making the ratio of the imaginary term μ" of the relative magnetic permeability at 0.11 THz to the imaginary term μ" of the relative magnetic permeability of the ultrahigh frequency absorption magnetic material at a frequency of 10 GHz within the above range, it is possible to exhibit higher absorption characteristics in a wider frequency band.

[0131] By making the ultra-high frequency absorption magnetic material of this embodiment contain α-Fe rare earth-iron-nitrogen system magnetic powder, ultra-wide frequency band ultra-high frequency absorption can be achieved in 1GHz~1THz, for example, it is expected that the uniaxial crystalline magnetic anisotropic materials such as hexagonal ferrite, boride, and ε iron oxide used at such ultra-high frequencies can be distinguished from magnetic materials with low relative magnetic permeability in a narrow band of about 10GHz. For in-plane crystalline magnetic anisotropic materials with lower resistivity than oxide materials but higher resistance than metal materials and capable of maintaining high frequency characteristics up to 1THz, it is a clear feature that the magnetic powder contains a phosphorus compound with high resistivity.

[0132] More specific uses of the ultra-high frequency absorbing magnetic material include: ultra-high frequency signals and spurious absorption components used in mobile communication devices, small mobile base stations and cloud base stations of 5G (5th Generation Mobile Communication System), 5G+ (5th Generation Plus Mobile Communication System) and 6G (6th Generation Mobile Communication System), their equipment, devices, antennas and other infrastructure equipment, ultra-high frequency signals and spurious absorption components for equipment / devices used in ITS (Intelligent Transport Systems), wireless HDMI (registered trademark) (wireless high-definition multimedia interface: High-Definition Multimedia Interface), wireless LAN (wireless local area network: Local Area Network), satellite broadcasting (Ka-band), etc., and electromagnetic noise absorption components for personal computers that mainly remove the 2nd to 7th harmonics.

[0133] The ultra-high frequency absorbing magnetic material of the present embodiment may contain a resin. The composite material of the magnetic material and the resin is called a bonded magnetic material, and the resin contained in the bonded magnetic material may be a thermosetting resin or a thermoplastic resin. As thermoplastic resins, there may be mentioned: polyphenylene sulfide (PPS), polyetheretherketone (PEEK), liquid crystal polymer (LCP), polyamide (PA), polypropylene (PP), polyethylene (PE), thermoplastic elastomers, etc. As thermosetting resins, there may be mentioned: epoxy resins, phenolic resins, urea resins, melamine resins, guanamine resins, unsaturated polyester resins, vinyl ester resins, diallyl phthalate resins, polyurethane resins, silicone resins, polyimide resins, alkyd resins, furan resins, dicyclopentadiene resins, acrylic resins, allyl carbonate resins, thermosetting elastomers generally referred to as rubbers, etc.

[0134] The content of the resin contained in the bonded magnetic material is preferably 0.1% by mass or more and 95% by mass or less. By making the content of the resin component 0.1% by mass or more, the impact resistance is further improved, and by making it 95% by mass or less, the extreme reduction of relative permeability and magnetization can be suppressed. In addition, for the bonded magnetic material of this embodiment, in the application requiring high relative permeability and impact resistance, for the same reasons as above, it is more preferably in the range of 0.5% by mass or more and 50% by mass or less, and in the case of being used as a transformer for high-frequency circuits with excellent efficiency, it is further preferably set to the range of 1% by mass or more and 15% by mass or less. In addition, in order to make the real term of the relative permeability particularly high as the magnetic material for magnetic field amplification of this embodiment and to make the absorption characteristics particularly good as an ultra-high frequency absorption material, although it is slightly different depending on the application, it is also preferably set to 15% by mass or less. Moldings that are not sintered and cured and do not contain resin, such as pressed powders using additives such as volatile organic solvents, are very brittle and are extremely difficult to use in magnetic field amplification materials such as wireless power supply coils and inductor cores that are loaded, or ultra-high frequency absorbing materials carried on 5G+ and 6G mobile devices that are frequently transported and subjected to a large amount of impact. In addition, molded bodies that contain a large number of penetrating air layers, such as pressed powders that have been press-formed at a pressure of less than 1.5 GPa, will deteriorate in impact resistance due to oxidation degradation or extreme embrittlement when exposed to temperatures above 50°C for a long time, so there is a tendency to be unsuitable for use at high temperatures. Therefore, in the molded body for the above-mentioned purposes, the content of the resin is preferably 0.1% by mass or more and 95% by mass or less, more preferably 0.5% by mass or more and 50% by mass or less, and further preferably 1% by mass or more and 15% by mass or less.

[0135] The resin composite for bonding magnetic materials can be obtained, for example, as follows: using a mixer, a phosphorus compound, an α-Fe rare earth-iron-nitrogen magnetic powder and a resin are mixed and / or kneaded at 180°C or higher and 300°C or lower; or, the α-Fe rare earth-iron-nitrogen magnetic powder and a resin are mixed and / or kneaded. For example, the α-Fe rare earth-iron-nitrogen magnetic powder and a resin are mixed using a mixer, and then kneaded and extruded using a twin-screw extruder, and the resulting strands are naturally cooled and then cut into a size of several mm using a granulator, thereby obtaining a granular resin composite for bonding magnetic materials of the present embodiment.

[0136] The bonded magnetic material of the present embodiment can be manufactured by molding a resin compound using an appropriate molding machine. Specifically, for example, the resin compound melted in the drum of the molding machine can be injection molded in a mold to which a magnetic field is applied so that the easy magnetization axes are aligned (orientation process), thereby obtaining a magnetic field oriented molded bonded magnetic material. In addition, by calendering and hot pressing the above-mentioned granular resin compound, sheet-shaped bonded magnetic material sheets for magnetic field amplification and bonded magnetic material sheets for ultra-high frequency absorption can be produced. By calendering it to a thickness of more than 20 μm and less than 200 μm, a magnetic material for magnetic field amplification with a high real number term of relative magnetic permeability can be made, for example, it can be suitably used as a magnetic material molded body sheet for magnetic field amplification for RFID tags, and can be used as a magnetic material molded body sheet for ultra-high frequency absorption for mobile devices.

[0137] <<Method for producing α-Fe rare earth-iron-nitrogen magnetic powder>>

[0138] The method for producing α-Fe-containing rare earth-iron-nitrogen magnetic powder of the present embodiment includes: a phosphorus treatment step, in which an inorganic acid is added to a slurry containing rare earth R (R is at least one selected from Y, Ce, Pr, Nd, Gd, Tb, Dy, Ho, Er, Tm, Lu and Sm, and when Sm is contained, Sm is less than 50 atomic% relative to the total R component), Fe, and N, water, and a phosphorus-containing substance, to form a phosphorus compound coating on the rare earth-iron-nitrogen magnetic powder, thereby obtaining a rare earth-iron-nitrogen magnetic powder having a phosphorus compound coating; and an oxidation step, in which the rare earth-iron-nitrogen magnetic powder having a phosphorus compound coating is heat-treated in an oxygen-containing atmosphere at a temperature of not less than 350°C and not more than 600°C.

[0139] [Phosphorus treatment process]

[0140] In the phosphorus treatment step, an inorganic acid is added to a slurry of rare earth-iron-nitrogen magnetic powder containing R, Fe and N, water, and a phosphorus-containing substance to obtain a rare earth-iron-nitrogen magnetic powder having a phosphorus compound coating. The rare earth-iron-nitrogen magnetic powder having a phosphorus compound coating is formed by a phosphorus compound (such as iron phosphate, neodymium phosphate, etc.) precipitated by a reaction between a metal component (such as iron, neodymium, etc.) contained in the rare earth-iron-nitrogen magnetic powder and a phosphorus component (such as phosphoric acid) contained in the phosphorus-containing substance. In addition, it is preferred that the rare earth-iron-nitrogen magnetic powder having a phosphorus compound coating is formed by precipitating a phosphorus compound on the surface of the rare earth-iron-nitrogen magnetic powder and coating at least a portion of the surface of the rare earth-iron-nitrogen magnetic powder (such coating is referred to as "phosphorus compound coating". The portion formed by such coating is referred to as a "phosphorus compound coating portion"). It should be noted that, compared with the case where no inorganic acid is added, by adding an inorganic acid in the present embodiment to adjust the pH of the slurry, the precipitation amount of the phosphorus compound can be increased. Therefore, a phosphorus compound-coated rare earth-iron-nitrogen magnetic powder having a thick coating thickness (also referred to as film thickness) can be obtained, tanδ and phase angle θ can be increased, and the magnetic field amplification characteristics can be improved. In addition, according to the present embodiment, by setting the solvent to water, phosphorus compounds such as phosphates with small particle sizes can be precipitated compared with the case where an organic solvent is used, and therefore, a rare earth-iron-nitrogen magnetic powder having a dense phosphorus compound coating can be obtained, which has a tendency to easily obtain excellent efficiency in the high frequency region and excellent absorption characteristics in the ultra-high frequency region.

[0141] The method for making a slurry containing a rare earth-iron-nitrogen magnetic powder containing R, Fe and N, water, and a phosphorus-containing substance is not particularly limited. For example, it can be obtained by mixing a rare earth-iron-nitrogen magnetic powder and a phosphorus-containing substance solution containing a phosphorus-containing substance with water as a solvent. The content of the rare earth-iron-nitrogen magnetic powder in the slurry is preferably 1% by mass or more and 50% by mass or less, and more preferably 5% by mass or more and 20% by mass or less from the perspective of productivity. The content of the phosphorus-containing substance in the slurry is not particularly limited. When the phosphorus-containing substance is phosphoric acid and is composed only of hydrogen and phosphoric acid components (PO4), the content is, for example, 0.01% by mass or more and 10% by mass or less in terms of PO4 conversion. From the perspective of the reactivity and productivity of the metal component and the phosphoric acid component, it is preferably 0.05% by mass or more and 5% by mass or less.

[0142] As phosphorus-containing substances, there can be mentioned: phosphorus element and its combination, phosphoric acid compounds such as orthophosphoric acid, heteropolyacid compounds such as phosphotungstic acid and phosphomolybdic acid, salts of phosphorus-containing compounds such as phosphoric acid compounds and heteropolyacid compounds with metal ions or ammonium ions, organic phosphorus compounds such as phosphate esters, phosphites, and phosphine oxides, iron phosphide, phosphor bronze, Fe-BP-Cu, Fe-Nb-BP alloys and other phosphorus-containing metals, etc.

[0143] When the phosphorus-containing substance is a phosphoric acid compound, an aqueous phosphoric acid solution can be obtained by mixing the phosphoric acid compound with water. As the phosphoric acid compound, there can be mentioned: for example, phosphates such as orthophosphoric acid, sodium dihydrogen phosphate, sodium monohydrogen phosphate, ammonium dihydrogen phosphate, ammonium monohydrogen phosphate, zinc phosphate, calcium phosphate, hypophosphorous acid, hypophosphite, pyrophosphate, polyphosphoric acid, etc., and organic phosphoric acid. Only one of these can be used, or two or more can be used in combination. In addition, for the purpose of improving the water resistance and corrosion resistance of the coating and the magnetic properties of the magnetic powder, oxygen-containing acid salts such as molybdates, tungstates, vanadates, chromates, oxidants such as sodium nitrate and sodium nitrite, chelating agents such as EDTA, etc. can be used as additives. Among phosphorus-containing substances, from the viewpoint of controlling the reaction and the coating amount, preferred are inorganic phosphoric acids such as orthophosphoric acid, pyrophosphoric acid, and polyphosphoric acid, and phosphate compounds such as phosphates thereof with Na, Ca, Pb, Zn, Fe, Y, Ce, Pr, Nd, Gd, Tb, Dy, Ho, Er, Tm, Lu, Sm, ammonium, and the like.

[0144] The concentration of phosphoric acid in the phosphoric acid aqueous solution (PO4 conversion amount) is preferably 5% by mass or more and 50% by mass or less, and is more preferably 10% by mass or more and 30% by mass or less from the perspective of the solubility, storage stability, and ease of chemical conversion treatment of the phosphoric acid compound. The pH of the phosphoric acid aqueous solution is preferably 1 or more and 4.5 or less, and is more preferably 1.5 or more and 4 or less from the perspective of easily controlling the precipitation rate of phosphate. The pH can be adjusted by dilute hydrochloric acid, dilute sulfuric acid, etc.

[0145] In the phosphorus treatment process, the slurry is made acidic by adding an inorganic acid, and the pH is preferably adjusted to be greater than 1 and less than 4.5, more preferably greater than 1.6 and less than 3.9, and further preferably greater than 2 and less than 3. When the pH is less than 1, the rare earth-iron-nitrogen magnetic powders agglomerate with each other, starting from the phosphorus compounds precipitated locally in large quantities, so that there is a tendency for tanδ and phase angle θ to deteriorate in the high-frequency region and μ" to decrease in the ultra-high frequency region. If the pH exceeds 4.5, the precipitation amount of phosphorus compounds such as phosphates decreases, so that there is a tendency for tanδ and phase angle θ to deteriorate in the high-frequency region and μ" to decrease in the ultra-high frequency region. As inorganic acids to be added, hydrochloric acid, nitric acid, sulfuric acid, boric acid, and hydrofluoric acid can be mentioned. In the phosphorus treatment process, it is preferred to add inorganic acids at any time to reach the above-mentioned pH range. From the perspective of waste liquid treatment, inorganic acids can be used, and organic acids can also be used in combination according to the purpose. As organic acids, acetic acid, formic acid, tartaric acid, etc. can be mentioned.

[0146] The phosphorus treatment step may be performed so that the phosphorus content in the obtained magnetic powder reaches 0.02 mass % or more. The phosphorus content in the magnetic powder obtained in the phosphorus treatment step is preferably 0.05 mass % or more, more preferably 0.15 mass % or more. The phosphorus content in the magnetic powder obtained in the phosphorus treatment step is preferably 4 mass % or less, more preferably 2 mass % or less, and further preferably 1 mass % or less. When the phosphorus content is 0.02 mass % or more, the coating effect brought about by the phosphorus compound tends to be further improved. When it is 4 mass % or less, the aggregation of rare earth-iron-nitrogen magnetic powders with the phosphorus compound as the starting point can be suppressed, and there is a tendency that tanδ and phase angle θ deteriorate in the high frequency region and μ" decreases in the ultra-high frequency region. In the case of making a magnetic material for magnetic field amplification with particularly excellent efficiency and a magnetic material for ultra-high frequency absorption with excellent absorption characteristics, the phosphorus content is preferably 0.15 mass % or more and 1 mass % or less. It should be noted that the phosphorus content of the entire volume of the magnetic powder can be measured using ICP-AES (ICP emission spectrometry). In addition, the phosphorus compound The local phosphorus content of the magnetic powder phase in the material-coated powder and the phosphorus compound coating portion can be measured using STEM-EDX line analysis. In addition, the phosphorus (P) atomic concentration in the phosphorus compound coating portion is preferably 1 atomic % or more, more preferably 5 atomic % or more. In addition, the P atomic concentration in the phosphorus compound coating portion can be 25 atomic % or less, preferably 15 atomic % or less. When the phosphorus content in the phosphorus compound coating portion is less than 1 atomic %, the electrical insulation of the phosphorus compound tends to be difficult to function. When it exceeds 25 atomic %, there is the following tendency: not only the real term of the relative magnetic permeability in the high-frequency region and the imaginary term of the relative magnetic permeability in the ultra-high frequency region are reduced, but also the corrosion resistance performance is reduced.

[0147] The phosphorus treatment step can be performed in the following manner: a region (R high concentration region) having a rare earth (R) atom concentration higher than the R atom concentration in the rare earth (R)-iron-nitrogen magnetic powder as the base material is provided in the phosphorus compound coating portion present on the surface of the obtained magnetic powder. The R atom concentration in the R high concentration region can be set to 1.05 times or more of the R atom concentration in the core region in the α-Fe rare earth-iron-nitrogen magnetic powder, preferably 1.1 times or more, more preferably 1.2 times or more, and further preferably 1.5 times or more. In addition, the R atom concentration in the R high concentration region can be set to, for example, 4 times or less of the R atom concentration in the core region in the α-Fe rare earth-iron-nitrogen magnetic powder. Here, the R high concentration region is a region including a layer showing a peak of P (phosphorus) in the STEM-EDX line analysis of the α-Fe rare earth-iron-nitrogen magnetic powder. The thickness of the R high concentration region can be, for example, 1 nm or more, preferably 3 nm or more and 150 nm or less, more preferably 10 nm or more and 100 nm or less, and further preferably 20 nm or more and 80 nm or less. The atomic concentration (atomic %) of each element in the R high concentration region can be obtained by averaging the atomic concentration in the phosphorus compound coating portion in the STEM-EDX line analysis. As a rare earth element (R), for example, Nd can be used. In this case, the Nd atomic concentration can be used as a benchmark for the Nd high concentration region for evaluation.

[0148] The pH of the slurry containing rare earth-iron-nitrogen magnetic powder, water, and phosphorus-containing material is adjusted to a range of 1 or more and 4.5 or less, preferably for 10 minutes or more, and more preferably for 30 minutes or more from the viewpoint of reducing the thickness of the thin portion of the coating. In the initial stage of pH maintenance, the pH rises quickly, so the interval of adding the inorganic acid for pH control is short. As the coating proceeds, the pH change gradually becomes gentle, and the interval of adding the inorganic acid becomes longer, thereby determining the end point of the reaction.

[0149] [Oxidation step after phosphorus treatment]

[0150] The rare earth-iron-nitrogen magnetic powder having a phosphorus compound coating obtained by the phosphorus treatment process is heat treated at a temperature of 350°C to 600°C in an oxygen-containing atmosphere to oxidize it. Based on the oxidation treatment, it can be considered that the interface between the phosphorus compound coating and the rare earth-iron-nitrogen magnetic powder and the surface of the rare earth-iron-nitrogen magnetic powder is oxidized to form an α-Fe-containing region that is disproportionately divided into a nano-α-Fe separation phase and an R nitrogen oxide phase. As a result, a magnetic material for magnetic field amplification with improved tanδ and phase angle θ in the high-frequency region and a magnetic material with high μ" absorption characteristics in the ultra-high frequency region can be obtained.

[0151] In addition, in the oxidation process after the phosphorus treatment, based on the phosphorus compound coating, there is a situation where iron oxide is released and precipitated on the surface of the α-Fe rare earth-iron-nitrogen magnetic powder. This is a phenomenon caused by the discharge of excess iron components from the first coating when the phosphorus compound coating is transformed from the eutectic and mixed crystal of iron phosphate and / or phosphate M, rare earth phosphate to a single phase of rare earth phosphate in the "oxidation process after phosphorus treatment". The iron oxide phase can be any one or more of hematite, magnetite, ferrite, and wutrite, and the iron oxide phase is mostly hematite. In addition, there are cases where the iron oxide is combined with the surface of the α-Fe rare earth-iron-nitrogen magnetic powder and the case where it is separated. In applications that require better efficiency, it is preferred to preliminarily combine the iron oxide with the surface of the α-Fe rare earth-iron-nitrogen magnetic powder, and in applications that require higher μ', it can be separated. As a method for separating the iron oxide phase, mechanical knocking using a roller, etc., and only dissolving the iron oxide phase by reaction with an acid can be cited.

[0152] The oxidation treatment is performed by heat treating the phosphorus treated magnetic powder in an oxygen-containing atmosphere. The reaction atmosphere preferably contains oxygen in an inert gas such as nitrogen or argon. The oxygen concentration is preferably 3% by volume or more and 21% by volume or less, more preferably 3.5% by volume or more and 10% by volume or less. In the oxidation reaction, gas exchange is preferably performed at a flow rate of 2L / min or more and 10L / min or less relative to 1kg of the magnetic powder.

[0153] The temperature during the oxidation treatment is 350°C to 600°C, preferably 380°C to 550°C, more preferably 400°C to 500°C, and further preferably 420°C to 480°C. When the temperature is lower than 350°C, the formation of the α-Fe-containing region is insufficient, and the real term of the relative magnetic permeability in the high-frequency region tends to decrease. When the temperature exceeds 600°C, the magnetic powder tends to decompose excessively. The reaction time is preferably 3 hours to 10 hours.

[0154] It is known that the thermal decomposition temperature of the rare earth-iron-nitrogen magnetic powder in the core region is about 550~650℃. In addition, it is also known that oxidative degradation occurs above 200℃ in an oxygen-containing atmosphere. Among them, it is previously unknown that it is used as an excellent α-Fe-containing rare earth-iron-nitrogen magnetic material after heating to a temperature close to the thermal decomposition temperature in an atmosphere containing oxygen. It can be considered that after a dense film is made on the rare earth-iron-nitrogen magnetic powder by the phosphorus treatment disclosed in the present invention, a heat treatment is performed in an oxygen-containing atmosphere. In order to prevent excessive thermal decomposition of the core region, a disproportionation reaction slowly begins from the surface of the rare earth-iron-nitrogen magnetic powder under the phosphorus compound coating, and α-Fe is separated and dispersed from the matrix at the nanometer level, thereby producing the α-Fe-containing rare earth-iron-nitrogen magnetic material of the present invention. It is completely unexpected that a magnetic material made by a step that did not exist in the past has excellent efficiency and high μ'.

[0155] The mechanism of forming the α-Fe containing region can be considered as follows, for example. Oxygen is slowly supplied through the phosphorus compound coating on the surface of the rare earth-iron-nitrogen powder and the interface between the rare earth-iron-nitrogen powder and the rare earth-iron-nitrogen powder, and the reaction between the rare earth-iron-nitrogen material and oxygen slowly proceeds from the surface and / or the interface (oxidation step), thereby the rare earth-iron-nitrogen material is transformed into a disproportionate layer of the α-Fe phase and the R nitride phase, and a specific "α-Fe containing region" is generated in which phase separation occurs at the nanometer level. At this time, if there is no phosphorus compound coating on the surface of the α-Fe containing rare earth-iron-nitrogen magnetic powder of the present invention, the rare earth-iron-nitrogen magnetic powder is simply oxidized, and nitrogen gas is lost into the atmosphere, and the reaction is more rapid than that of the present invention. As a result, it changes to a mixture of (1) α-Fe or iron oxide and (2) rare earth oxide. Since there is no lattice conformity in (1) and (2), unlike the α-Fe-containing region of the α-Fe-containing rare earth-iron-nitrogen magnetic material of the present invention, the α-Fe is regularly arranged and tends to become a non-oriented, non-uniform phase.

[0156] [Silicon dioxide treatment process]

[0157] The magnetic powder that has undergone the phosphorus treatment step and the oxidation step can be subjected to a silica treatment as needed. By forming a silica film on the magnetic powder, oxidation resistance can be improved. The silica film can be formed, for example, by mixing an alkyl silicate, magnetic powder, and an alkaline solution.

[0158] [Silane coupling treatment process]

[0159] The magnetic powder treated with silica can be further treated with a silane coupling agent. By subjecting the magnetic powder formed with a silica film to a silane coupling treatment, a silane coupling agent film can be formed on the silica film, which can improve the magnetic properties of the magnetic powder and improve the wettability of the resin and the strength of the molded body. The silane coupling agent is not particularly limited as long as it is selected according to the type of resin, and examples thereof include: for example, γ-(2-aminoethyl)aminopropyltrimethoxysilane, γ-(2-aminoethyl)aminopropylmethyldimethoxysilane, γ-methacryloxypropyltrimethoxysilane, γ-methacryloxypropylmethyldimethoxysilane, N-β-(N-vinylbenzylaminoethyl)-γ-aminopropyltrimethoxysilane / hydrochloride, γ-glycidylpropyltrimethoxysilane, Silane, γ-mercaptopropyltrimethoxysilane, methyltrimethoxysilane, methyltriethoxysilane, vinyltriacetoxysilane, γ-chloropropyltrimethoxysilane, hexamethylenedisilazane, γ-anilinopropyltrimethoxysilane, vinyltrimethoxysilane, octadecyl[3-(trimethoxysilyl)propyl]ammonium chloride, γ-chloropropylmethyldimethoxysilane, γ-mercaptopropylmethyldimethoxysilane, methyltrichlorosilane, dimethyldichlorosilane, trimethylchlorosilane, vinyltri Chlorosilane, vinyl tri(β-methoxyethoxy)silane, vinyl triethoxysilane, β-(3,4-epoxycyclohexyl)ethyl trimethoxysilane, γ-glycidylpropylmethyldiethoxysilane, N-β(aminoethyl)γ-aminopropyltrimethoxysilane, N-β(aminoethyl)γ-aminopropylmethyldimethoxysilane, γ-aminopropyltriethoxysilane, N-phenyl-γ-aminopropyltrimethoxysilane, ureidopropyltriethoxysilane, γ-isocyanatepropyltriethoxy Silane, polyethoxydimethylsiloxane, polyethoxymethylsiloxane, bis(trimethoxysilylpropyl)amine, bis(3-triethoxysilylpropyl)tetrasulfide, γ-isocyanatepropyltrimethoxysilane, vinylmethyldimethoxysilane, 1,3,5-N-tris(3-trimethoxysilylpropyl)isocyanurate, tert-butylcarbamatetrialkoxysilane, N-(1,3-dimethylbutylidene)-3-(triethoxysilyl)-1-propylamine and other silane coupling agents. These silane coupling agents can be used alone or in combination. The amount of the silane coupling agent added is preferably 0.2 parts by mass or more and 0.8 parts by mass or less, and more preferably 0.25 parts by mass or more and 0.6 parts by mass or less, relative to 100 parts by mass of the magnetic powder. If the content is less than 0.2 parts by mass, the effect of the silane coupling agent is small, while if it exceeds 0.8 parts by mass, the magnetic properties of the magnetic powder and the molded product tend to be reduced due to aggregation of the magnetic powder.

[0160] It should be noted that the silica treatment step and / or the silane coupling treatment step may not be performed; or after these treatment steps, isopropyl triisostearoyl titanate, isopropyl tri(N-aminoethyl-aminoethyl) titanate, isopropyl tri(dioctyl pyrophosphate acyloxy) titanate, tetraisopropyl bis(dioctyl phosphite acyloxy) titanate, tetraisopropyl titanate, tetrabutyl titanate, tetraoctyl bis(ditridecyl phosphite acyloxy) titanate, isopropyl trioctanoyl titanate, isopropyl triisostearo ... The surface of magnetic powder is treated with titanium coupling agents such as propyl tridodecylbenzenesulfonyl titanate, isopropyl tri(dioctylphospho) titanate, bis(dioctylpyrophospho) ethylene titanate, isopropyl dimethacryloyl stearoyl titanate, tetra(2,2-diallyloxy-1-butyl)bis(ditridecylphosphite) titanate, and isopropyl triisopropylphenyl titanate, and aluminum, zirconium, chromium, iron, and tin coupling agents such as diisopropylacetyl alkoxyaluminum. When the powder after this treatment is made into a bonded magnetic material, the affinity with the added resin is improved, the isolated dispersion of the α-Fe rare earth-iron-nitrogen magnetic powder is more remarkable, and electrical insulation between powders can be achieved, and sometimes excellent efficiency in the high frequency range and excellent absorption characteristics in the ultra-high frequency range are exhibited.

[0161] The magnetic powder after the phosphorus treatment step, the oxidation step, the silica treatment step, or the silane coupling treatment step can be filtered, dehydrated, and dried by a common method.

[0162] The real term of the relative magnetic permeability of the rare earth-iron-nitrogen magnetic powder can be increased by making the distribution of the particle size uniform. The uniform distribution of the particle size can be performed by a general dry classification method or a wet classification method. The uniform distribution of the particle size can be performed at any time before the phosphoric acid treatment, after the phosphorus treatment step, after the oxidation step, after the silica treatment step, or after the silane coupling treatment step.

[0163] The rare earth-iron-nitrogen magnetic powder used in the production method of the present embodiment contains R (wherein R is at least one selected from Y, Ce, Pr, Nd, Gd, Tb, Dy, Ho, Er, Tm, Lu, and Sm, and when Sm is contained, Sm is less than 50 atomic % relative to the whole R component), Fe, and N. R is at least one selected from Y, Ce, Pr, Nd, Gd, Tb, Dy, Ho, Er, Tm, Lu, and Sm. From the viewpoint of achieving stability in raw material supply and high relative permeability, Nd, Y, Ce, Pr, Gd, and Dy are preferred, and Nd, Y, Ce, and Pr are more preferred from the viewpoint of cost. Here, when Sm is contained, the content of Sm is less than 50 atomic % relative to the whole R component, but more preferably less than 20 atomic %. In particular, when the content of Nd or Pr is 50 atomic % or more of the entire R component, a magnetic material having a higher relative magnetic permeability and a magnetic material having further improved tanδ and phase angle θ can be obtained. In addition, from the perspective of oxidation resistance and cost balance, the content of Nd or Pr is preferably 70 atomic % or more, the resource is abundant, the absolute value of the crystal magnetic anisotropy magnetic field (an index showing the magnitude of magnetic anisotropy) is large, and the absorption performance at a higher ultra-high frequency is high, so a rare earth-iron-nitrogen magnetic powder containing NdFeN with a Nd content of 100 atomic % is particularly preferred.

[0164] The content of Fe in the rare earth-iron-nitrogen magnetic powder is preferably 40 atomic % or more and 87 atomic % or less, and more preferably 50 atomic % or more and 85 atomic % or less.

[0165] Example

[0166] The present disclosure will be described in more detail by the following examples and the like, but the present disclosure is not limited to these examples and the like.

[0167] The evaluation methods performed in the Examples are as follows.

[0168] (1) Element content

[0169] The concentrations of P and Mo in the magnetic powder were measured using ICP emission spectrometry (ICP-AES SPS3500 manufactured by Hitachi High-Tech Science Co., Ltd.) The concentrations of O and N in the magnetic powder were measured using an oxygen / nitrogen analyzer (EMGA-820 manufactured by Horiba, Ltd.).

[0170] (2) XRD and α-Fe peak intensity ratio and half-value width

[0171] For the magnetic powder, the XRD spectrum was measured using a powder X-ray crystal diffractometer (manufactured by Rigaku Corporation, X-ray wavelength: CuKα). The measurement was carried out under the following conditions: acceleration voltage 40 kV, tube current 20 mA, step size 2θ=0.02 between 10<2θ<90. In the XRD diffraction pattern, the ratio (I) / (II) of the diffraction peak intensity (I) of the (110) plane of α-Fe and the peak intensity (II) of the strongest line of the rare earth-iron-nitrogen compound in the core region was calculated. The peaks of (I) and (II) were calculated by taking the peak near 2θ=44° as the strongest line of the (110) plane of α-Fe and the peak at 2θ=41.5° as the strongest line of the rare earth-iron-nitrogen compound. In addition, the peak half-value width used in Scherrer's formula was calculated from the peak of the (110) plane of α-Fe.

[0172] (3) Average particle size

[0173] The average particle size of the magnetic powder was measured using a laser diffraction particle size distribution device (MALVERN Inst. MASTERSIZER 2000).

[0174] (4) Complex relative permeability measurement (1MHz~1GHz)

[0175] The magnetic powder and epoxy resin as a thermosetting resin were mixed so that the content of the magnetic powder was 97% by mass, and then kneaded to produce a resin composite. The resin composite was added to a mold with an inner diameter of 3.1 mm and an outer diameter of 8 mm, and after molding with a pressure of 0.8 GPa, a heat curing treatment was performed at 150°C for 2 hours in a vacuum to produce a toroidal molded body. Using this sample, the complex relative permeability in the frequency range of 1 MHz to 1 GHz was evaluated using an impedance analyzer (HP4291B, manufactured by Hewlett-Packard Company) based on the inductance value obtained by a single-turn inductor type test device.

[0176] (5) STEM-EDX analysis and TEM-ED analysis

[0177] The STEM analysis of the surface of the magnetic powder is carried out as described below. First, the obtained magnetic powder was subjected to cross-sectioning and thin-sectioning by FIB (focused ion beam) after carbon coating. The obtained sample was measured using STEM (manufactured by FEI, model Talos F200X; acceleration voltage 200kV) and STEM-EDX attached to STEM (system: manufactured by FEI, model SuperX, detector: SDD detector manufactured by Bruker). Line analysis was performed from the outside to the inside of the magnetic powder at the step length described later, and the continuous atomic concentration changes of each constituent element were observed. At this time, depending on the measurement site, there is a risk of detecting a large amount of carbon (C) in the resin used to make the cross-section sample, so the atomic concentration is calculated as the total of elements other than C. In addition, TEM-ED was used to evaluate the crystallinity and orientation of the α-Fe-containing region of the magnetic powder.

[0178] (6) Complex relative permeability measurement (1GHz~18GHz)

[0179] The magnetic powder and the polyamide elastomer as a thermoplastic resin were mixed so that the content of the magnetic powder was 91.7% by mass. After kneading, a resin sheet of about 1 mm thick was made by hot pressing. A ring-shaped sample with an inner diameter of 3.04 mm and an outer diameter of 7 mm was cut from the resin sheet. Using this sample, the complex relative permeability in the frequency range of 1 to 18 GHz was evaluated by the S parameter value obtained by the coaxial method using a network analyzer (N5290A, Keysight Technologies).

[0180] Production Example 1

[0181] Nd2Fe2O3 with an average particle size of about 15 μm without phosphorus treatment was prepared by precipitation method using iron sulfate and neodymium sulfate as raw materials as follows: 17 N3 magnetic powder.

[0182] [Preparation of Nd-Fe sulfuric acid solution]

[0183] 5.0 kg of FeSO4・7H2O was mixed and dissolved in 2.0 kg of pure water. 0.45 kg of Nd2O3 and 0.70 kg of 70% sulfuric acid were further added and stirred thoroughly to completely dissolve. Then, pure water was added to the obtained solution to adjust the final Fe concentration to 0.726 mol / L and the Nd concentration to 0.106 mol / L, thus preparing a Nd-Fe sulfuric acid solution.

[0184] [Precipitation process]

[0185] In 20 kg of pure water maintained at 40°C, the entire amount of the prepared Nd-Fe sulfuric acid solution was added dropwise while stirring for 70 minutes from the start of the reaction, and 15% ammonia water was added dropwise to adjust the pH to 7-8. Thus, a slurry containing Nd-Fe hydroxide was obtained. After the obtained slurry was washed with pure water by decantation, the hydroxide was separated into solid and liquid. The separated hydroxide was dried in an oven at 100°C for 10 hours.

[0186] [Oxidation process]

[0187] The hydroxide obtained in the precipitation step was calcined in air at 1030° C. for 1 hour. After cooling, a red Nd—Fe oxide was obtained as a raw material powder.

[0188] [Pre-treatment process]

[0189] 100 g of Nd-Fe oxide was placed in a steel container with a volume thickness of 10 mm. The container was placed in a furnace, depressurized to 100 Pa, and heated to a pretreatment temperature of 850° C. while introducing hydrogen gas, and maintained in this state for 15 hours, thereby obtaining a partial oxide of black powder.

[0190] [Reduction process]

[0191] 60 g of the partial oxide obtained in the pretreatment step was mixed with 19.2 g of metal calcium having an average particle size of about 6 mm and placed in a furnace. After the furnace was evacuated, argon gas (Ar gas) was introduced. The temperature was raised to 1045° C. and maintained for 45 minutes, thereby obtaining Fe—Nd alloy particles.

[0192] [Nitriding process]

[0193] Next, the temperature in the furnace was cooled to 100° C., and then vacuum evacuated. While introducing nitrogen gas, the temperature was raised to 450° C. and maintained in this state for 23 hours, thereby obtaining a bulk product containing magnetic powder.

[0194] [Water washing process]

[0195] The block product obtained by the nitriding process was added to 3 kg of pure water and stirred for 30 minutes. After standing, the supernatant was discharged by decantation. The addition to pure water, stirring and decantation were repeated 10 times. Then, 2.5 g of 99.9% acetic acid was added and stirred for 15 minutes. After standing, the supernatant was discharged by decantation. The addition to pure water, stirring and decantation were repeated twice, and then after dehydration and drying, mechanical crushing was performed to obtain Nd2Fe 17 N3 magnetic powder (average particle size about 15μm).

[0196] Comparative Example 1

[0197] Using the Nd2Fe prepared in Preparation Example 1 17 N3 magnetic powder was phosphorus treated as described below. As a phosphoric acid treatment solution, it was prepared as follows: 85% original phosphoric acid: sodium dihydrogen phosphate: sodium molybdate dihydrate = 1:6:1 mass ratio was mixed, and the pH was adjusted to 2 with pure water and dilute hydrochloric acid, and the PO4 concentration was adjusted to 20 mass%. The Nd-Fe-N series magnetic powder obtained by the water washing process was stirred in a dilute hydrochloric acid of 1000g water: 70g hydrogen chloride for 1 minute, and after removing the surface oxide film and dirt components, the surface oxide film and dirt components were repeatedly drained and filled with water until the conductivity of the supernatant reached 100μS / cm or less, thereby obtaining a slurry containing 10 mass% of Nd-Fe-N series anisotropic magnetic powder. While stirring the obtained slurry, all 100g of the prepared phosphoric acid treatment solution was put into the treatment tank, and then, by adding 6 mass% hydrochloric acid at any time, the pH of the phosphoric acid treatment reaction slurry was controlled in the range of 2.0±0.1 and maintained for 40 minutes. Next, suction filtration, dehydration, and vacuum drying were performed to obtain Nd—Fe—N-based anisotropic magnetic powder having a phosphorus compound coating portion.

[0198] Examples 1-4, Comparative Examples 2-3

[0199] For 300 g of the Nd-Fe-N based anisotropic magnetic powder with a phosphorus compound coating of Comparative Example 1, the temperature was slowly increased from room temperature in an atmosphere of a mixed gas of nitrogen and air (oxygen concentration 4 vol %, 5 L / min), and heat treated at the highest temperature recorded in Table 1 for 8 hours to obtain the rare earth-iron-nitrogen based magnetic powder of Examples 1 and 2 after oxidation treatment (average particle size of about 15 μm).

[0200] Using the Nd-Fe-N based anisotropic magnetic powder with a phosphorus compound coating and an average particle size of about 13 μm obtained by the same operation as in Comparative Example 1, heat treatment was carried out at the maximum temperature recorded in Table 1 for 8 hours in the same manner as in Examples 1 and 2, to obtain rare earth-iron-nitrogen based magnetic powders of Examples 3 and 4 and Comparative Examples 2 and 3 after oxidation treatment (the average particle size is shown in Table 1).

[0201] The magnetic powders prepared in Examples 1 to 4 and Comparative Examples 1 to 3 were used to measure the content of each element of P, Mo, O, and N and the α-Fe peak intensity ratio by the above method. The measurement results are shown in Table 1 together with the oxidation temperature after phosphorus treatment and the average particle size. In addition, the XRD patterns of the magnetic powders prepared in Examples 1 to 4 and Comparative Examples 1 to 3 are shown in Table 1. Figure 1 .

[0202] According to Table 1, the oxygen O content in the magnetic powder does not change substantially at a treatment temperature up to 320°C. This indicates that the oxidation of the magnetic powder is suppressed due to the presence of the phosphorus compound coating. In addition, at a treatment temperature of 350°C or higher, O gradually increases, and the broad peak intensity of α-Fe begins to rise. This indicates that at a treatment temperature of 350°C or higher, R oxynitride phases and nano-sized α-Fe begin to form, and an α-Fe-containing region begins to form. In addition, the diffraction peak of hematite begins to grow from 380°C, and it is believed that an iron oxide layer is formed on the outside of the phosphorus compound coating.

[0203]

[0204] Comparative Example 1 ( Figure 2A and Figure 2B )、Example 1( Figure 3A and 3B )、Example 2( Figure 4A and 4B , Figure 5A and 5B ), and Example 4 ( Fig. 6A and 6B , Fig. 7A and 7B , Figure 8 ) of the magnetic powder surface. Only Example 2 was observed using STEM (manufactured by JEOL Ltd., model JEM-F200; acceleration voltage 200 kV) and STEM-EDX (system: manufactured by JEOL Ltd., model SD100HR, detector: Dry SD detector manufactured by JEOL Ltd.) attached to STEM. In each STEM, EDX, and TEM, the magnification was 530900 times ( Figure 2A ), 640000 times ( Figure 3A ), 2,500,000 times ( Figure 4A ), 250,000 times ( Figure 5A ), 320000 times ( Fig. 6A ), 14000 times ( Fig. 7A ), 74000 times ( Figure 8 ) were observed. The obtained STEM images, STEM-EDX images and line analysis results are shown in Figures 2 to 7. In each line analysis, the step size was 0.18 nm ( Figure 2B )、0.18nm( Figure 3B )、0.16nm( Figure 4B )、1.6nm( Figure 5B )、0.36nm( Figure 6B )、8.2nm( Figure 7B ).

[0205] according to Figure 2A (Comparative Example 1) It is believed that only the core region as the base material exists inside the phosphorus compound coating. Figure 3A (Example 1), Figure 4A (Example 2), Fig. 6A In Example 4, a phase containing nano-sized Fe and Nd is generated inside the coating. Figure 4A In the STEM-EDX images, the contrast of the sea-island structure in the α-Fe-containing region was observed when focusing on Fe or Nd, and the composition ratio of elements near each region of the "sea" and "island" was determined. It was confirmed that the composition ratio of Fe near the "island" region was higher and the composition ratio of Nd and O was lower than that near the "sea" region. Figure 3A The enlarged image of the α-Fe-containing region is shown in Fig.10 .Will Fig.10 The atomic concentrations of N, O, Fe, and Nd in Area 1 and Area 2 are shown in Table 2.

[0206]

[0207] As shown in Table 2, more Nd, N, and O were detected in Area 2 than in Area 1, while more Fe was detected in Area 1. Based on this result and the XRD result, it is speculated that the layer containing more Fe is the α-Fe phase, and the region containing more Nd is a phase containing neodymium oxide, neodymium nitride, or neodymium oxynitride. It should be noted that due to the averaging of the information in the depth direction corresponding to the thickness of the thin film sample (about 100nm) and the scattering of the electron beam in the sample, N, O, and Nd were also detected in the α-Fe phase, and Fe was also detected in the phase containing neodymium oxide, neodymium nitride, or neodymium oxynitride. It can be inferred that: Figure 3A In the structure, there is an "island" area in the form of Area 1, which is an R oxide phase (or R nitride phase) with more oxygen contained in Nd than in Fe, and an "island" area in the form of Area 2, which is a "sea" area with more Fe. Figure 3B (Example 1), Figure 4B (Example 2), Figure 6B (Example 4) It is considered that Examples 1, 2, and 4 contain a phosphorus compound and an iron oxide layer as a coating.

[0208] Based on the STEM-EDX analysis and XRD spectrum, it is inferred that the nano-scale Fe is α-Fe, and based on the STEM-EDX and line analysis results, it is inferred that the phase containing Nd contains O and N (R oxynitride phase). In addition, the nano-scale α-Fe and R oxynitride phases become larger in Example 4. The film thickness of the α-Fe-containing region is about 20nm (Example 1), about 400nm (Example 2), and about 4μm (Example 4). In addition, the line analysis results near the surface of Example 2 and Example 4 and the entire α-Fe-containing region ( Figure 4B , Figure 5B , Figure 6B , Figure 7B ), the cross-sectional shapes near the most surface and the interface of each phase are different, which is caused by the different step lengths in the online analysis. In addition, in Example 4, broad peaks of NdFeO3, which are presumed to be perovskite structures, were observed near 2θ=23° and 33° in the XRD spectrum.

[0209] Figure 8 The STEM image and electron diffraction image of the α-Fe-containing region of Example 4 are shown. Figure 8 The right image is based on

[111] incidence Figure 8 The left figure shows the electron diffraction pattern of α-Fe in a circular area with a diameter of 200 nm. Figure 8 The bright hexagonal diffraction points on the right side are attributed to the {110} of α-Fe. Fig. 6A ), it is inferred that the size of the α-Fe phase in this part is uniformly arranged below 10 nm. Figure 8 Clear spots are observed in the left image, so it can be considered that the α-Fe phase is arranged and oriented in one direction within a diameter of 200nm. However, in addition to this, satellites with lower brightness are observed at equal intervals between the origin, the diffraction points of {110} and {220} derived from α-Fe. It can be considered that these are diffraction points derived from the R nitride phase that surrounds the α-Fe phase and lattice matches the α-Fe, and the matrix phase of the α-Fe phase and the R nitride phase are crystallized, arranged and oriented within a range of 200nm in the α-Fe-containing region. It can be considered that by forming such an orderly structure, it becomes a magnetic powder that highly balances electrical insulation and magnetic coupling.

[0210] In addition, by Figure 1 The peak of the (110) face of α-Fe in the XRD spectrum was calculated according to the Scherrer formula to obtain the respective crystallite diameters (6.8nm (Example 1), 8.7nm (Example 2), 8.9nm (Example 3), and 8.6nm (Example 4)). The calculated values ​​are larger than the particle sizes observed by STEM-EDX, which is believed to be due to the fact that not only the α-Fe phase but also some crystals containing lattice-matched rare earth oxides are reflected in the diffraction peaks.

[0211] Using the magnetic powders of Comparative Examples 1 to 3 and Examples 1 to 4, samples for measuring complex relative magnetic permeability at 1 MHz to 1 GHz were prepared by the above method (ring-shaped bodies (resin addition amount 6 mass %) with densities of 5.85 (Comparative Example 1), 5.38 (Comparative Example 2), 5.54 (Comparative Example 3), 5.66 (Example 1), 5.27 (Example 2), 5.40 (Example 3), and 4.97 (Example 4)). The results of the frequency dependence of the complex relative magnetic permeability at 1 MHz to 100 MHz measured by the above method are shown in FIG. Fig. 9 The evaluation results of high frequency characteristics are shown in Table 3.

[0212] In Comparative Examples 1 to 3, θ1 / θ2 is less than 0.7, and in Examples 1 to 4, θ1 / θ2 is greater than 0.8. This is believed to be because the oxidation process after the phosphorus treatment leads to the formation of an α-Fe-containing region, and the electrical insulation becomes higher. In addition, although Examples 2 and 3 have lower density than Comparative Examples 1 to 3, μ' increases. This is believed to be because the oxidation process after the phosphorus treatment leads to the formation of an α-Fe-containing region, and the effect of magnetic coupling increases. In addition, in Examples 1 to 4, θ at 13 MHz is greater than 85° (tan δ is less than 0.0875), and the loss is low, so they can be appropriately used as antenna materials for RFID. In Comparative Examples 1 to 3, when θ is less than 85° (tan δ exceeds 0.0875), the loss is high and the efficiency is low.

[0213]

[0214] Example 5 and Comparative Example 4

[0215] By classifying the magnetic powder obtained by the same operation as in Comparative Example 1, a phosphorus-treated rare earth-iron-nitrogen magnetic powder with an average particle size of about 4 μm was produced (Comparative Example 4). In addition, by classifying the magnetic powder obtained by the same operation as in Example 1, an α-Fe-containing rare earth-iron-nitrogen magnetic powder with an average particle size of about 4 μm was produced (Example 5). For the determination of the average particle size of Comparative Example 4 and Example 5, a laser diffraction particle size distribution measuring device (HELOS & RODOS manufactured by Nippon Laser Co., Ltd.) was used. A density of about 5.0 g / cm 3 The resin sheet was tested at 1 GHz and 7.6 GHz (the frequencies at which μ" in Example 5 takes a maximum value), and the value of μ" at 10 GHz was evaluated. The results are shown in Table 4. In the region of 1 to 10 GHz, the magnetic material of Example 5 showed a higher μ" than that of Comparative Example 4.

[0216]

[0217] Example 6

[0218] By classifying the magnetic powder obtained by the same operation as in Example 2, an α-Fe rare earth-iron-nitrogen magnetic powder having an average particle size of about 17 μm was produced. For the measurement of the average particle size, a laser diffraction particle size distribution measuring device (HELOS & RODOS manufactured by Japan Laser Co., Ltd.) was used. A ring-shaped molded body (density 5.58) was produced by mixing with a resin in the same manner as in Examples 1 to 4, and an impedance analyzer was used to evaluate the complex relative magnetic permeability in the frequency range of 1 MHz to 1 GHz based on the inductance value obtained by a single-turn inductor type test device. The results are shown in Table 5. In addition, the results of Example 2 are also recorded in Table 5. The results of the frequency dependence of the complex relative magnetic permeability at 1 MHz to 100 MHz measured by the above method are shown in Fig.11 Compared with Example 2, the classified magnetic powder of Example 6 showed a higher μ'.

[0219]

[0220] The invention disclosed herein may include the following aspects, for example.

[0221] [1] An α-Fe rare earth-iron-nitrogen magnetic powder having:

[0222] Nuclear region; and

[0223] In the α-Fe containing region outside the core region,

[0224] The core region contains rare earth R (R is at least one selected from Y, Ce, Pr, Nd, Gd, Tb, Dy, Ho, Er, Tm, Lu and Sm, and when Sm is contained, Sm is less than 50 atomic % relative to the whole R component), Fe, and N.

[0225] The α-Fe-containing region includes α-Fe and at least one selected from the group consisting of an oxide, a nitride, and an oxynitride of the rare earth R.

[0226] [2] The α-Fe-containing rare earth-iron-nitrogen magnetic powder according to [1], wherein

[0227] The α-Fe-containing region comprises:

[0228] A nanocrystal containing at least one selected from the group consisting of an oxide, a nitride, and a nitride oxide of the rare earth element R; and

[0229] Contains nanocrystals of α-Fe.

[0230] [3] The α-Fe-containing rare earth-iron-nitrogen magnetic powder according to [1] or [2], wherein:

[0231] The thickness of the α-Fe containing region is not less than 0.01% and less than 50% of the average particle size of the α-Fe containing rare earth-iron-nitrogen based magnetic powder.

[0232] [4] The α-Fe-containing rare earth-iron-nitrogen magnetic powder according to any one of [1] to [3], wherein

[0233] The α-Fe-containing region has a thickness of 1 nm or more and 10 μm or less.

[0234] [5] The α-Fe-containing rare earth-iron-nitrogen magnetic powder according to any one of [1] to [4], wherein

[0235] The core region comprises a rare earth-iron-nitrogen compound,

[0236] In the XRD diffraction pattern, the ratio (I) / (II) of the diffraction peak intensity (I) of the (110) plane of α-Fe to the peak intensity (II) of the strongest line of the rare earth-iron-nitrogen compound is 0.01 or more and less than 10.

[0237] [6] The α-Fe-containing rare earth-iron-nitrogen magnetic powder according to any one of [1] to [5], wherein the real term of the relative magnetic permeability at 10 MHz is 6 or more.

[0238] [7] The α-Fe-containing rare earth-iron-nitrogen magnetic powder according to any one of [1] to [6], wherein

[0239] When the phase angle at 100 MHz is θ1 and the phase angle at 2 MHz is θ2, θ1 / θ2 is equal to or greater than 0.8.

[0240] [8] The α-Fe-containing rare earth-iron-nitrogen magnetic powder according to any one of [1] to [7], wherein the phase angle θ at 13 MHz is 85° or more.

[0241] [9] A magnetic material for amplifying a magnetic field, comprising the α-Fe rare earth-iron-nitrogen magnetic powder according to any one of [1] to [8].

[0242]

[10] The magnetic material for amplifying a magnetic field according to [9], further comprising a resin.

[0243]

[11] The magnetic material for amplifying a magnetic field according to [9] or

[10] , which can be used for wireless power supply.

[0244]

[12] A magnetic material for ultra-high frequency absorption, comprising the α-Fe rare earth-iron-nitrogen magnetic powder according to any one of [1] to [8].

[0245]

[13] An α-Fe rare earth-iron-nitrogen magnetic powder having:

[0246] Nuclear region, and

[0247] In the α-Fe containing region outside the core region,

[0248] The core region includes rare earth R (R is at least one selected from Y, Ce, Pr, Nd, Gd, Tb, Dy, Ho, Er, Tm, Lu and Sm, and when Sm is included, Sm is less than 50 atomic % relative to the entire R component), Fe and N,

[0249] The α-Fe containing region has a sea-island structure including a sea region and an island region, wherein the atomic concentration (%) of Fe in the island region is higher than that in the sea region, and the atomic concentration (%) of rare earth elements R and O in the island region is lower than that in the sea region.

[0250]

[14] A method for producing α-Fe rare earth-iron-nitrogen magnetic powder, the method comprising:

[0251] a phosphorus treatment step of adding an inorganic acid to a slurry comprising rare earth-iron-nitrogen magnetic powder, water, and a phosphorus-containing substance to form a phosphorus compound coating on the rare earth-iron-nitrogen magnetic powder, thereby obtaining a rare earth-iron-nitrogen magnetic powder having a phosphorus compound coating, wherein the rare earth-iron-nitrogen magnetic powder comprises rare earth R (R is at least one selected from Y, Ce, Pr, Nd, Gd, Tb, Dy, Ho, Er, Tm, Lu, and Sm, and when Sm is included, Sm is less than 50 atomic % relative to the entire R component), Fe, and N; and

[0252] In the oxidation step, the rare earth-iron-nitrogen magnetic powder having the phosphorus compound coating is heat treated in an oxygen-containing atmosphere at a temperature of 350° C. to 600° C.

[0253]

[15] The method for producing an α-Fe-containing rare earth-iron-nitrogen magnetic powder according to

[14] , wherein:

[0254] In the phosphorus treatment step, the inorganic acid is added to adjust the pH of the slurry to 1 or more and 4.5 or less.

[0255] Industrial Applicability

[0256] According to the present disclosure, an α-Fe-containing rare earth-iron-nitrogen magnetic powder having excellent magnetic field amplification characteristics and ultra-high frequency absorption characteristics can be obtained. The magnetic powder can be appropriately used as a magnetic material for magnetic field amplification and a magnetic material for ultra-high frequency absorption. The magnetic material for magnetic field amplification and the magnetic material for ultra-high frequency absorption can be used for the following materials: transformers, magnetic heads, inductors, reactors, cores (magnetic cores), magnetic yokes, RFID tags, wireless power supplies, and other high-frequency and ultra-high frequency transmission and reception elements, which are mainly used as power equipment and information communication related equipment in high frequency or ultra-high frequency areas, and materials that can be used for antennas; magnetic materials used for microwave elements, magnetostrictive elements, magnetoacoustic elements, magnetic recording elements, Hall elements, magnetic sensors, current sensors, rotation sensors, electronic compasses, and other sensors that use magnetic fields; further, magnetic materials that can be used for electromagnetic noise absorption materials, electromagnetic wave absorption materials, magnetic shielding materials, etc. to suppress malfunctions caused by unnecessary electromagnetic wave interference; magnetic materials that can be used for noise removal inductors and other inductor element materials or noise filtering materials to remove noise from signals in the high frequency or ultra-high frequency area.

Claims

1. An α-Fe rare earth-iron-nitrogen magnetic powder, comprising: Nuclear region; and In the α-Fe containing region outside the core region, in, The core region contains rare earth elements R, Fe, and N, R is at least one selected from Y, Ce, Pr, Nd, Gd, Tb, Dy, Ho, Er, Tm, Lu, and Sm, and when Sm is contained, Sm is less than 50 atomic % relative to the entire R component. The α-Fe-containing region includes α-Fe and at least one selected from the group consisting of an oxide, a nitride, and an oxynitride of the rare earth R.

2. The α-Fe-containing rare earth-iron-nitrogen magnetic powder according to claim 1, wherein: The α-Fe-containing region comprises: A nanocrystal containing at least one selected from the group consisting of an oxide, a nitride, and a nitride oxide of the rare earth element R; and Contains nanocrystals of α-Fe.

3. The α-Fe-containing rare earth-iron-nitrogen magnetic powder according to claim 1 or 2, wherein: The thickness of the α-Fe containing region is not less than 0.01% and less than 50% of the average particle size of the α-Fe containing rare earth-iron-nitrogen based magnetic powder.

4. The α-Fe-containing rare earth-iron-nitrogen magnetic powder according to any one of claims 1 to 3, wherein The α-Fe-containing region has a thickness of 1 nm or more and 10 μm or less.

5. The α-Fe-containing rare earth-iron-nitrogen magnetic powder according to any one of claims 1 to 4, wherein The core region comprises a rare earth-iron-nitrogen compound, In the XRD diffraction pattern, the ratio (I) / (II) of the diffraction peak intensity (I) of the (110) plane of α-Fe to the peak intensity (II) of the strongest line of the rare earth-iron-nitrogen compound is 0.01 or more and less than 10. 6 . The α-Fe-containing rare earth-iron-nitrogen magnetic powder according to claim 1 , wherein the real term of the relative magnetic permeability at 10 MHz is 6 or more.

7. The α-Fe-containing rare earth-iron-nitrogen magnetic powder according to any one of claims 1 to 6, wherein When the phase angle at 100 MHz is θ1 and the phase angle at 2 MHz is θ2, θ1 / θ2 is equal to or greater than 0.

8. 8 . The α-Fe-containing rare earth-iron-nitrogen magnetic powder according to claim 1 , wherein a phase angle θ at 13 MHz is 85° or more. 9 . A magnetic material for amplifying a magnetic field, comprising the α-Fe-containing rare earth-iron-nitrogen magnetic powder according to claim 1 . 10 . The magnetic material for amplifying a magnetic field according to claim 9 , further comprising a resin.

11. The magnetic material for amplifying a magnetic field according to claim 9 or 10, which can be used for wireless power supply. 12 . A magnetic material for ultrahigh frequency absorption, comprising the α-Fe-containing rare earth-iron-nitrogen magnetic powder according to claim 1 .

13. An α-Fe rare earth-iron-nitrogen magnetic powder, comprising: Nuclear region, and In the α-Fe containing region outside the core region, in, The core region contains rare earth elements R, Fe and N, R is at least one selected from Y, Ce, Pr, Nd, Gd, Tb, Dy, Ho, Er, Tm, Lu and Sm, and when Sm is contained, Sm is less than 50 atomic % relative to the entire R component. The α-Fe containing region has a sea-island structure including a sea region and an island region, wherein the atomic concentration (%) of Fe in the island region is higher than that in the sea region, and the atomic concentration (%) of rare earth elements R and O in the island region is lower than that in the sea region.

14. A method for producing α-Fe rare earth-iron-nitrogen magnetic powder, the method comprising: a phosphorus treatment step of adding an inorganic acid to a slurry comprising rare earth-iron-nitrogen magnetic powder, water, and a phosphorus-containing substance to form a phosphorus compound coating on the rare earth-iron-nitrogen magnetic powder, thereby obtaining a rare earth-iron-nitrogen magnetic powder having a phosphorus compound coating, wherein the rare earth-iron-nitrogen magnetic powder comprises rare earths R, Fe, and N, R is at least one selected from the group consisting of Y, Ce, Pr, Nd, Gd, Tb, Dy, Ho, Er, Tm, Lu, and Sm, and when Sm is contained, Sm is less than 50 atomic % relative to the entire R component; and In the oxidation step, the rare earth-iron-nitrogen magnetic powder having the phosphorus compound coating is heat treated in an oxygen-containing atmosphere at a temperature of 350° C. to 600° C.

15. The method for producing α-Fe-containing rare earth-iron-nitrogen magnetic powder according to claim 14, wherein: In the phosphorus treatment step, the inorganic acid is added to adjust the pH of the slurry to 1 or more and 4.5 or less.

Citation Information

Patent Citations

  • Magnetic material for high frequency wave, and method for production thereof

    WO2008136391A1